CLIMATE CHANGE , LAND DEGRADATION , AND DESERTIFICATION IN THE MEDITERRANEAN ENVIRONMENT - Wrachien, D De; Ragab, R (Desertification in the Mediterranean Region a Security Issue)
Until the early seventies land degradation and desertification were not considered a major issue in most Mediterranean regions. Traditional agricultural systems were believed to be able to keep those processes in check. Thus low priority was assigned to research programmes and projects on soil erosion and conservation, preference being given to the impact of farm machinery on soil structure and compaction along with the role of organic matter in the soil. In the eighties and early nineties the agricultural practices introduced in sloping land under cultivation in the Mediterranean in previous decades were identified as a major contributor to soil degradation. The unprecedented efforts to increase crop yields and maximize profit, made possible by the technological revolution in agriculture, had triggered in the agricultural ecosystem the onset of soil degradation due to hydrological phenomena that proved detrimental both to soil fertility and to the landscape causing devastating and permanent damage. In addition, it was recognized that research activities were too fragmentary to be able to cope with the demands of implementing sound soil conservation measures. The Mediterranean climate is characterised by hot dry summers and mild wet winters. The region frequently suffers from years of scant rainfall and many areas are afflicted by severe drought. The UK Hadley Centre's global climate model has been run on a monthly basis for the Mediterranean countries to predict the percent variation in rainfall and temperature with respect to mean monthly values. Scenarios developed using the model show that for the wet season (October-March), by the year 2050 rainfall could increase in central and eastern Spain, northern France, northern Italy and the Alps by up to 15%, against a decrease of about 10% to 15% in the southern Mediterranean. For the same period, the temperature in the northern Mediterranean is predicted to increase by 1.25° to 2.25°C, compared to an increase of between 1.5° and 2.5°C in the southern Mediterranean. The projections also show that for the dry season (April to September), by the year 2050 rainfall is likely to decrease over much of the Basin. Decreased precipitation is predicted to be accompanied by a rise in temperature of between 1.5 and 2.75°C in the northern regions and 1.75° and 3.0°C in the southern Mediterranean. Reduced precipitation during the summer has a major impact on irrigation and tourism, which both increase the pressure on water supplies during the dry period. To combat these problems, the European Community (EC), in collaboration with other international organizations, has funded various programmes and projects for mitigating drought and assessing and preventing land degradation and desertification. In this context, the paper describes the main features and characteristics of some of these programmes and projects and proposes new approaches to environmental policies, in order to: • • • • • assess, forecast and mitigate adverse impacts of drought; better understand soil erosion, land degradation and desertification processes; identify preventive, protective and remedial measures; address quantity and quality of natural resources in an integrated context; support innovation and participatory strategies. The importance and role of institutional strengthening, sound financial and managerial frameworks, availability of human resources involved, research thrust, technology transfer and networking improvement are also highlighted.
Keywords: climate change; EU programs; land degradation and desertification

Changes in DNA methylation fingerprint of Quercus ilex trees in response to experimental field drought simulating projected climate change - Rico, L; Ogaya, R; Barbeta, A; Penuelas, J (Plant Biology, 2014)
Rapid genetic changes in plants have been reported in response to current climate change. We assessed the capacity of trees in a natural forest to produce rapid acclimation responses based on epigenetic modifications. We analysed natural populations of Quercus ilex, the dominant tree species of Mediterranean forests, using the methylation-sensitive amplified polymorphism (MSAP) technique to assess patterns and levels of methylation in individuals from unstressed forest plots and from plots experimentally exposed to drought for 12 years at levels projected for the coming decades. The percentage of hypermethylated loci increased, and the percentage of fully methylated loci clearly decreased in plants exposed to drought. Multivariate analyses exploring the status of methylation at MSAP loci also showed clear differentiation depending on stress. The PCA scores for the MSAP profiles clearly separated the genetic from the epigenetic structure, and also significantly separated the samples within each group in response to drought. Changes in DNA methylation highlight the large capacity of plants to rapidly acclimate to changing environmental conditions, including trees with long life spans, and our results demonstrate those changes. These changes, although unable to prevent the decreased growth and higher mortality associated with this experimental drought, occurred together with a dampening in such decreases as the long-term treatment progressed.
Keywords: climate change; DNA methylation; Drought; methylation-sensitive amplified polymorphism

Converting probabilistic tree species range shift projections into meaningful classes for management. - Hanewinkel, Marc; Cullmann, Dominik A; Michiels, Hans-Gerd; Kändler, Gerald (Journal of environmental management, 2014)
The paper deals with the management problem how to decide on tree species suitability under changing environmental conditions. It presents an algorithm that classifies the output of a range shift model for major tree species in Europe into multiple classes that can be linked to qualities characterizing the ecological niche of the species. The classes: i) Core distribution area, ii) Extended distribution area, iii) Occasional occurrence area, and iv) No occurrence area are first theoretically developed and then statistically described. The classes are interpreted from an ecological point of view using criteria like population structure, competitive strength, site spectrum and vulnerability to biotic hazards. The functioning of the algorithm is demonstrated using the example of a generalized linear model that was fitted to a pan-European dataset of presence/absence of major tree species with downscaled climate data from a General Circulation Model (GCM). Applications of the algorithm to tree species suitability classification on a European and regional level are shown. The thresholds that are used by the algorithm are precision-based and include Cohen's Kappa. A validation of the algorithm using an independent dataset of the German National Forest Inventory shows good accordance of the statistically derived classes with ecological traits for Norway spruce, while the differentiation especially between core and extended distribution for European beech that is in the centre of its natural range in this area is less accurate. We hypothesize that for species in the core of their range regional factors like forest history superimpose climatic factors. Problems of uncertainty issued from potentially applying a multitude of modelling approaches and/or climate realizations within the range shift model are discussed and a way to deal with the uncertainty by revealing the underlying attitude towards risk of the decision maker is proposed.
Keywords: Accuracy-based probability threshold; Bioclimatic envelope; climate change; Range shift model; Tree species distribution; Tree species suitability

Defoliation triggered by climate induced effects in Spanish ICP Forests monitoring plots - de la Cruz, Ana C.; Gil, Paula M.; Fernández-Cancio, Ángel; Minaya, Mayte; Navarro-Cerrillo, Rafael M.; Sánchez-salguero, Raúl; Grau, José Manuel; De, Ana C.; Gil, Paula M.; Fernández-Cancio, Ángel; Minaya, Mayte; Navarro-Cerrillo, Rafael M.; et al. (Forest Ecology and Management, 2014)
In a context of global change, climate impacts can trigger defoliation processes in different forest species. The ICP Forests network estimates the level of forest defoliation over time in different European countries. Those data are used to related defoliation with potential causal factors. In European Southwestern forests, climate change appears to be the detonating factor of generalized defoliation. The objectives of this study were: (i) identity defoliation trends in forest trees at network of Spanish ICP Forests monitoring plots and, (ii) find out if there are underlying climate factors that trigger defoliation process along the time. The spatiotemporal synchronization of the defoliation response was analyzed with cross-correlation using COFECHA software. The relationship between the 88 climatic variables proposed and defoliation was analyzed using Correlated Component Regression models (CCR models) and Discriminant Analysis (DA). The significance of the variables in each model was compared using contingency tables. A peak of defoliation was observed in the mid-1990s with no recovered to the initial values of the early 1990s. The behavior of the different tree species with respect to defoliation, synchronized both in time and space, involves one or several factors that have a general and similar effect on forests in Spain. The most significant factors related to defoliation were the thermal-related factors, particularly average temperatures in April and June and the thermal oscillation of both the current year and the previous year. Only one drought indicator as statistically significant was identified (A, duration of aridity in months) and suggests that it is of limited relevance in the Spanish forest defoliation conditions.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: climate change; Cross-correlation; crown condition; Forest decline; Mediterranean forests; Synchronization

Direct and indirect effects of tree canopy facilitation in the recruitment of Mediterranean oaks - Caldeira, Maria C.; Ibáñez, Inés; Nogueira, Carla; Bugalho, Miguel N.; Lecomte, Xavier; Moreira, Andreia; Pereira, João S. (Journal of Applied Ecology, 2014)
* Tree recruitment in Mediterranean ecosystems is strongly limited at the seedling stage by drought. Increasing evidence shows the critical positive role of the canopy nurse effect on seedling survival which results from direct and indirect, positive and negative interactions between species. * Most studies, however, have only focused on the effects of tree canopy on water and light, ignoring other critical factors affecting seedling regeneration, such as canopy effects on high temperatures and the competing herb biomass. * Here, we evaluate how tree canopy cover and removal of herbs affect the survival and growth of seedlings of two dominant Mediterranean Quercus species during a 3-year study. We use an integrated model that combines several data sets to quantify and predict regeneration dynamics along environmental gradients of soil moisture, temperature and light. * Low soil moisture, increased soil temperature and herb biomass negatively affected seedling survival of both Quercus species. Seedling growth was positively associated with increasing soil moisture and light. * Although tree canopy cover directly facilitated seedling survival in both Quercus species, it also negatively affected herb biomass and thus indirectly facilitated the survival of Quercus suber, but not of Quercus ilex seedlings at low levels of soil moisture. * Overall, tree canopies increased seedling survival but not growth during the establishment phase, mainly by ameliorating the effects of low soil moisture and high temperatures. Tree canopy indirectly facilitated survival of Q. suber seedlings by negatively affecting the competing herb layer. * Synthesis and applications. To improve tree recruitment and conserve Mediterranean Quercus woodlands, the removal of herbs should be integrated into management plans for dry habitats. Interactions between abiotic and biotic factors may also effect the regeneration of these tree species. In particular, a healthy tree canopy will become important for providing conditions to facilitate seedling establishment if these habitats become drier and warmer, as predicted by some climate change scenarios.
Keywords: climate change; herb management; high temperatures; positive interactions; Quercus ilex; Quercus suber; tree recruitment

Drought events determine performance of Quercus ilex seedlings and increase their susceptibility to Phytophthora cinnamomi - Corcobado, Tamara; Cubera, Elena; Juárez, Enrique; Moreno, Gerardo; Solla, Alejandro (Agricultural and Forest Meteorology, 2014)
More frequent weather extremes are expected to occur in the Mediterranean region within the present context of climate change. These extremes could affect forests and plant diseases driven by pathogens. It is hypothesised that simulation of weather extremes during Quercus ilex growth will influence early performance and susceptibility to the invasive oomycete Phytophthora cinnamomi. In 2010, 140 Q. ilex seedlings were subjected to three watering regimes under greenhouse conditions: waterlogging (W), water stress (S) and optimal watering regime for growth (C). During the second vegetative period, conditions were altered to create the following scenarios: WW, WS, SS, SW and CC. After the second vegetative period, plants were artificially infested with P. cinnamomi. Holm oak (Q. ilex) was more sensitive to flooding in the first year of growth than in the second year. The altered scenarios produced plants with a lower fine-to-total root ratio than plants in unaltered scenarios. Plants with the highest growth rates maintained their relatively rapid growth and photosynthetic activity under altered scenarios. However, plants with the highest growth rates became the plants with the lowest growth rates when two consecutive years of drought occurred, indicating a trade-off by Q. ilex in growth investment, observed only if the water stress scenario persists. Seedlings were more sensitive to water shortage than to waterlogging, especially if they encountered a dry scenario during the first year. Exposure to drought events increased seedling mortality rates after P. cinnamomi infection. Waterlogging combined with subsequent water deprivation was the worst scenario when soil was infested with P. cinnamomi, causing 100% mortality of plants.
Keywords: climate change; Drought; Flooding; Invasive pathogen; Oak decline; Weather extremes

Foliar CO2 in a holm oak forest subjected to 15 years of climate change simulation - Ogaya, Romà; Llusia, Joan; Barbeta, Adrià; Asensio, Dolores; Liu, Daijun; Alessio, Giorgio Arturo; Penuelas, Josep (Plant Science, 2014)
A long-term experimental drought to simulate future expected climatic conditions for Mediterranean forests, a 15% decrease in soil moisture for the following decades, was conducted in a holm oak forest since 1999. Net photosynthetic rate, stomatal conductance and leaf water potential were measured from 1999 to 2013 in Quercus ilex and Phillyrea latifolia, two co-dominant species of this forest. These measurements were performed in four plots, two of them received the drought treatment and the two other plots were control plots. The three studied variables decreased with increases in VPD and decreases in soil moisture in both species, but the decrease of leaf water potential during summer drought was larger in P. latifolia, whereas Q. ilex reached higher net photosynthetic rates and stomatal conductance values during rainy periods than P. latifolia. The drought treatment decreased ca. 8% the net photosynthetic rates during the overall studied period in both Q. ilex and P. latifolia, whereas there were just non-significant trends toward a decrease in leaf water potential and stomatal conductance induced by drought treatment. Future drier climate may lead to a decrease in the carbon balance of Mediterranean species, and some shrub species well resistant to drought could gain competitive advantage relative to Q. ilex, currently the dominant species of this forest.
Keywords: climate change; Drought; mediterranean forest; phillyrea latifolia; photosynthetic rates; Quercus ilex

Future impacts of nitrogen deposition and climate change scenarios on forest crown defoliation. - De Marco, Alessandra; Proietti, Chiara; Cionni, Irene; Fischer, Richard; Screpanti, Augusto; Vitale, Marcello (Environmental pollution (Barking, Essex : 1987), 2014)
Defoliation is an indicator for forest health in response to several stressors including air pollutants, and one of the most important parameters monitored in the International Cooperative Programme on Assessment and Monitoring of Air Pollution Effects on Forests (ICP Forests). The study aims to estimate crown defoliation in 2030, under three climate and one nitrogen deposition scenarios, based on evaluation of the most important factors (meteorological, nitrogen deposition and chemical soil parameters) affecting defoliation of twelve European tree species. The combination of favourable climate and nitrogen fertilization in the more adaptive species induces a generalized decrease of defoliation. On the other hand, severe climate change and drought are main causes of increase in defoliation in Quercus ilex and Fagus sylvatica, especially in Mediterranean area. Our results provide information on regional distribution of future defoliation, an important knowledge for identifying policies to counteract negative impacts of climate change and air pollution.
Keywords: climate change; Crown defoliation; General regression models; Nitrogen deposition; Random forests analysis

Grass – woodland transitions : determinants and consequences for ecosystem functioning and provisioning of services - Sala, Osvaldo E; Maestre, Fernando T (Journal of Ecology, 2014)
1. A large fraction of grasslands world-wide is undergoing a rapid shift from herbaceous to woody- plant dominance, while in other parts of the world, the opposite transition from woodland to grassland is the dominant phenomenon. These shifts have received increasing attention in the ecological litera- ture during the last two decades due to their global extent and their impacts on ecosystem functioning. 2. This Special Feature includes a series of contributions on key topics within the study of grass– woodland transitions, including three articles addressing the drivers of these vegetation shifts and another three evaluating their ecological consequences. These articles, which include reviews, mod- elling and empirical studies, highlight the multiplicity of approaches and spatial scales being cur- rently used when studying grass–woodland transitions. 3. The first articles focus on the role of fire in driving the dynamics of mesic grasslands in the USA, on the effects of climate change on the transition zones between treeless vegetation, savanna and forest in tropical and subtropical Americas and on the role of the internal structure of vegetation as a determinant of grassland–woodland transitions. The articles devoted to exploring the conse- quences include a modelling study on the ecohydrological consequences of shrub removal in wes- tern North America and an empirical study aiming at understanding how abiotic and biotic attributes influence above-ground net productivity across Patagonian grasslands and shrublands, as well as a review of the consequences of brush management on the provision of ecosystem services. 4. Synthesis. Identifying the best actions to avoid or take advantage of grass–woodland transitions requires a mechanistic understanding of both the drivers of these shifts and their ecological conse- quences. The collection of reviews, empirical and modelling studies included in this Special Feature contributes to forecasting how ongoing global change will affect grass–woodland transitions and their consequences for the provisioning of ecosystem services from drylands, which account for a large fraction of Earth’s surface.
Keywords: climate change; ecosystem services; ecosystem–water dynamics; fire; Grasslands; inva- sion ecology; primary production; shrublands; vegetation shifts; woody-plant encroachment

Insight into the photosynthetic apparatus in evergreen and deciduous European oaks during autumn senescence using OJIP fluorescence transient analysis - Holland, V; Koller, S; Brüggemann, W (Plant Biology, 2014)
Climate change is one of the major issues nowadays, and Mediterranean broadleaf species have been suggested to fill possible future gaps created by climate change in Central European forests. To provide a scientific-based foundation for such practical strategies, it is important to obtain a general idea about differences and similarities in the physiology of Central European and Mediterranean species. In the present study, we evaluated the onset of leaf senescence of a broad spectrum of oak species under the Central European climate in a common garden experiment. Degradation of the photosynthetic apparatus of evergreen (Quercus ilex, Q. suber), semi-evergreen (Q. × turneri, Q. × hispanica) and deciduous oaks (Q. robur, Q. cerris, Q. frainetto, Q. pubescens) was monitored as chlorophyll content and analysed chlorophyll fluorescence induction transients. In the deciduous species, a significant decline in chlorophyll content was observed during autumn/winter, with Q. pubescens showing the slowest decline. Analysis of fluorescence induction transients revealed a significant decline in quantum efficiency of the primary photochemistry and reaction centre density and later, a decrease in quantum efficiency of end acceptor reduction. Alterations in fluorescence parameters were compared to the decline in chlorophyll content, which occurred much more slowly than expected from the fluorescence data. The evergreen species showed no decline in chlorophyll content, nor different chlorophyll a fluorescence induction behaviour despite temperature falling below 0 °C. The hybrids showed intermediate behaviour between their parental evergreen and deciduous taxa.
Keywords: chlorophyll fluorescence; climate change; portable fluorimeter; Quercus; Senescence; SPAD

Disparity in elevational shifts of European trees in response to recent climate warming - Rabasa, Sonia G; Granda, Elena; Benavides, Raquel; Kunstler, Georges; Espelta, Josep M; Ogaya, Romà; Penuelas, Josep; Scherer-Lorenzen, Michael; Gil, Wojciech; Grodzki, Wojciech; Ambrozy, Slawomir; Bergh, Johan; et al. (GLOBAL CHANGE BIOLOGY, 2013)
Predicting climate-driven changes in plant distribution is crucial for biodiversity conservation and management under recent climate change. Climate warming is expected to induce movement of species upslope and towards higher latitudes. However, the mechanisms and physiological processes behind the altitudinal and latitudinal distribution range of a tree species are complex and depend on each tree species features and vary over ontogenetic stages. We investigated the altitudinal distribution differences between juvenile and adult individuals of seven major European tree species along elevational transects covering a wide latitudinal range from southern Spain (37 degrees N) to northern Sweden (67 degrees N). By comparing juvenile and adult distributions (shifts on the optimum position and the range limits) we assessed the response of species to present climate conditions in relation to previous conditions that prevailed when adults were established. Mean temperature increased by 0.86 degrees C on average at our sites during the last decade compared with previous 30-year period. Only one of the species studied, Abies alba, matched the expected predictions under the observed warming, with a maximum abundance of juveniles at higher altitudes than adults. Three species, Fagus sylvatica, Picea abies and Pinus sylvestris, showed an opposite pattern while for other three species, such as Quercus ilex, Acer pseudoplatanus and Q. petraea, we were no able to detect changes in distribution. These findings are in contrast with theoretical predictions and show that tree responses to climate change are complex and are obscured not only by other environmental factors but also by internal processes related to ontogeny and demography.
Keywords: altitudinal gradient; climate change; FOREST; generalized additive models; Species distribution

Effect of wildfires on soil respiration in three typical Mediterranean forest ecosystems in Madrid, Spain - Uribe, C; Inclán, R; Sanchez, D M; Clavero, M A; Fernandez, A M; Morante, R; Cardena, A; Blanco, A; Van Miegroet, H (PLANT AND SOIL, 2013)
Mediterranean forests are vulnerable to numerous threats including wildfires due to a combination of climatic factors and increased urbanization. In addition, increased temperatures and summer drought lead to increased risk of forest fires as a result of climate change. This may have important consequences for C dynamics and balance in these ecosystems. Soil respiration was measured over 2 successive years in Holm oak (Quercus ilex subsp. ballota; Qi); Pyrenean Oak (Quercus pyrenaica Willd; Qp); and Scots pine (Pinus sylvestris L.; Ps) forest stands located in the area surrounding Madrid (Spain), to assess the long term effects of wildfires on C efflux from the soil, soil properties, and the role of soil temperature and soil moisture in the variation of soil respiration. Soil respiration, soil temperature, soil moisture, fine root mass, microbial biomass, biological and chemical soil parameters were compared between non burned (NB) and burned sites (B). The annual C losses through soil respiration from NB sites in Qi, Qp and Ps were 790, 1010, 1380 gCm(-2) yr(-1), respectively, with the B sites emitting 43 %, 22 % and 11 % less in Qi, Qp and Ps respectively. Soil microclimate changed with higher soil temperature and lower soil moisture in B sites after fire. Exchangeable cations and the pH also decreased. The total SOC stocks were not significantly altered, but 6-8 years after wildfires, there was still measurably lower fine root and microbial biomass, while SOC quality changed, indicated by lower the C/N ratio and the labile carbon and a relative increase in refractory SOC forms, which resulted in lower Q(10) values. We found long term effects of wildfires on the physical, chemical and biological soil characteristics, which in turn affected soil respiration. The response of soil respiration to temperature was controlled by moisture and changed with ecosystem type, season, and between B and NB sites. Lower post-burn Q(10) integrated the loss of roots and microbial biomass, change in SOC quality and a decrease in soil moisture.
Keywords: climate change; Pinus sylvestris; Quercus ilex; Quercus pyrenaica; soil parameters; Soil respiration; wildfires

Field-simulated droughts affect elemental leaf stoichiometry in Mediterranean forests and shrublands - Sardans, Jordi; Rivas-Ubach, Albert; Estiarte, Marc; Ogaya, Romà; Penuelas, Josep (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 2013)
This study evaluated the change induced by the year season and by experimentally induced drought on foliar element stoichiometry of the predominant woody species (Quercus ilex and Erica multiflora) in two Mediterranean ecosystems, a forest and a shrubland. This study is based in two long-term (11 yr) field experiments that simulated drought throughout the annual cycle. The effects of experimental droughts were significant but weaker than the changes produced by ontogeny and seasonality. Leaf N and P concentrations were higher in spring (the main growing season) in E. multiflora and, in Q. ilex in autumn (a period of additional growth). Leaf N:P ratios were lower in spring. In Q. ilex, the highest leaf K concentrations and leaf K:P ratios, and the lowest leaf C:K and N:K ratios, occurred in summer, the season when water stress was greatest. In E. multiflora, leaf K concentrations and K:P ratios were highest, and leaf C:K and N:K ratios were lowest in the plants from the drought-treated plots. The plant capacity to change K concentrations in response to seasonality and to drought is at least as great as the capacity to change N and P concentrations. The results underscore the importance of K and its stoichiometry relative to C, N and P in dry environments. These results indicate first, that N:P ratio shifts are not uniquely related to growth rate in Mediterranean plants but also to drought, and second, that there is a need to take into account K in ecological stoichiometry studies of terrestrial plants. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: climate change; Drought; Growth rate hypothesis; N:P; nitrogen; Ontogeny; phosphorus; Potassium

Intensity and timing of warming and drought differentially affect growth patterns of co-occurring Mediterranean tree species - Granda, Elena; Julio Camarero, J; Gimeno, Teresa E; Martínez-Fernández, Jesús; Valladares, Fernando (EUROPEAN JOURNAL OF FOREST RESEARCH, 2013)
Climate change involves warmer temperatures, altered precipitation patterns, increased climatic variability and, in Mediterranean regions, increased frequency and severity of droughts. Tree species may show different growth responses to these components of climatic change, which may trigger changes in forest composition and dominance. We assessed the influence of recent climatic changes on secondary growth of mature trees from four species co-occurring in a Mediterranean continental forest: Quercus ilex, Quercus faginea, Pinus nigra and Juniperus thurifera. We used dendrochronology to relate radial-growth variables \{[\}earlywood and latewood widths, basal area increment (BAI)] to annual and seasonal climatic variables for the period 1977-2007. Our results showed that Q. faginea BAI has declined, whereas J. thurifera BAI has increased over time while Q. ilex and P. nigra have maintained their growth rates. Growth was mainly favored by higher precipitations and tree size for all species. Reduced growth during extremely dry years was observed for all study species, but all of them except Q. faginea recovered their growth levels 2 years after drought. Our findings illustrate how the effects of climatic changes on growth should include analyses of seasonal climatic trends and extreme events such as severe droughts. We conclude that the seasonal timing of warming and precipitation alterations leading to drought events caused contrasting effects on growth of co-occurring Mediterranean tree species, compromising their future coexistence.
Keywords: climate change; Coexistence; Dendroecology; Drought; Mediterranean forests; Radial growth

Interspecific differences in tree growth and mortality responses to environmental drivers determine potential species distributional limits in Iberian forests - Benito-Garzón, Marta; Ruíz-Benito, PALOMA; Zavala, Miguel A. (Global Ecology and Biogeography, 2013)
Aim Tree growth may be enhanced by carbon dioxide fertilization unless drought stress becomes too severe, yet the likely increase in tree growth under a warmer climate is still controversial. Tree mortality has increased in some regions, but its multifactorial nature makes the prediction of likely global trends difficult. The aims of this work are: (1) to assess which abiotic, structural and competition factors influence tree growth and tree mortality in mainland Spain, and (2) to evaluate whether these processes would drive species distributions and would improve current niche model predictions. Location Continental Spain. Methods We projected species distributional models by integrating nonparametric tree growth and tree mortality models based on repeated surveys of diameter at breast height and mortality for 40,721 trees distributed in 45,301 plots, which include the 11 most common canopy tree species in continental Spain, as measured in the second and third National Forest Inventories, with a mean lag time of 11 years. Results Tree growth and tree mortality were explained by an assemblage of many factors, among which climate and competition played a key role. The accuracy of models including tree growth and tree mortality in predicting tree habitat suitability was comparable to classical niche models based on species occurrence. Projections under climate change showed for 9 out of 11 species, a likely increase in tree growth that would be counteracted by an increase in tree mortality, suggesting that even if growth rates increase, mortality would limit the species ranges under global warming expectations. Main conclusions Growth and mortality are major determinants of species distributions. Under future climate change expectations, our model suggests that growth may increase for some Iberian species, but even in this case, species ranges at the rear edge would be limited by an increase in mortality rates.
Keywords: climate change; demographic rates; national forest inventory; phenotypic variability; Spain; species distributional models; tree growth; tree mortality

Modeling the response of within-storm runoff and erosion dynamics to climate change in two Mediterranean watersheds: A multi-model, multi-scale approach to scenario design and analysis - Nunes, J. P.; Seixas, J.; Keizer, J. J. (CATENA, 2013)
Climate change in the Mediterranean is expected to lead to lower total rainfall and soil moisture, together with higher storm intensities; different vegetation types are expected to react positively or negatively to these and other changes. Climate change could therefore have positive or negative impacts on runoff and soil erosion during storms, and previous research has indicated that the impacts could be different at the field, hillslope and catchment scales. This problem was assessed for two Mediterranean watersheds by a combined application of the PROMES regional climate model, the SWAT continuous hydrological and vegetation model, and the MEFIDIS storm runoff and erosion model. PROMES results were used to estimate changes to storm rainfall intensity, while SWAT was applied with the PROMES results to estimate changes to soil moisture and saturation deficit, as well as vegetation cover. The results from both models were used to generate scenarios of changes to storm intensity (increasing), saturation deficit (increasing) and vegetation cover (increasing according to vegetation type). These scenarios were used as input for the MEFIDIS model to study the impacts of these changes on runoff and soil erosion across spatial scales for a set of storms. The simulation results indicate that (i) the increase in saturation deficit and vegetation cover is sufficient, in many cases, to decrease or counterbalance the impacts of increased storm intensity on soil erosion at all spatial scales; (ii) catchment sediment yield is noticeably more sensitive to the climate change scenarios than within-watershed soil erosion, mostly due to the impacts of changes to saturation deficit and vegetation cover on connectivity; (iii) within the watershed, impacts on soil erosion vary with landcover type, with croplands suffering the most negative impacts.
Keywords: climate change; Mediterranean watersheds; Modeling; soil erosion

Modeling the response of within-storm runoff and erosion dynamics to climate change in two Mediterranean watersheds: A multi-model, multi-scale approach to scenario design and analysis - Nunes, J P; Seixas, J; Keizer, J J (CATENA, 2013)
Climate change in the Mediterranean is expected to lead to lower total rainfall and soil moisture, together with higher storm intensities; different vegetation types are expected to react positively or negatively to these and other changes. Climate change could therefore have positive or negative impacts on runoff and soil erosion during storms, and previous research has indicated that the impacts could be different at the field, hillslope and catchment scales. This problem was assessed for two Mediterranean watersheds by a combined application of the PROMES regional climate model, the SWAT continuous hydrological and vegetation model, and the MEFIDIS storm runoff and erosion model. PROMES results were used to estimate changes to storm rainfall intensity, while SWAT was applied with the PROMES results to estimate changes to soil moisture and saturation deficit, as well as vegetation cover. The results from both models were used to generate scenarios of changes to storm intensity (increasing), saturation deficit (increasing) and vegetation cover (increasing according to vegetation type). These scenarios were used as input for the MEFIDIS model to study the impacts of these changes on runoff and soil erosion across spatial scales for a set of storms. The simulation results indicate that (i) the increase in saturation deficit and vegetation cover is sufficient, in many cases, to decrease or counterbalance the impacts of increased storm intensity on soil erosion at all spatial scales; (ii) catchment sediment yield is noticeably more sensitive to the climate change scenarios than within-watershed soil erosion, mostly due to the impacts of changes to saturation deficit and vegetation cover on connectivity; (iii) within the watershed, impacts on soil erosion vary with landcover type, with croplands suffering the most negative impacts.
Keywords: climate change; Mediterranean watersheds; Modeling; soil erosion

Non-invasive tools to estimate stress-induced changes in photosynthetic performance in plants inhabiting Mediterranean areas - Guidi, Lucia; Calatayud, Angeles (Environmental and Experimental Botany, 2013)
In Mediterranean areas, plants are concomitantly exposed to various abiotic stresses such as light intensity, water deficit, extremes in air temperature, air pollutants, etc. These environmental pressures adversely affect plant development. Changes in photosystem activity are an early response of plants to abiotic stresses. Therefore, chlorophyll (Chl) fluorescence and gas exchange, two non-invasive, rapid and inexpensive techniques for measuring photosynthesis in leaves, have been widely used by plant ecophysiologists to analyse plant responses to stressful conditions. Chl a fluorescence and gas exchange parameters can be indeed used to evaluate changes in photochemical and non-photochemical processes in photosystems associated with electron transport, CO2 fixation, and heat dissipation. In this review, we focus our analysis on the effects of different abiotic stresses on the photochemistry of Mediterranean plants using Chl a fluorescence and gas exchange measurements. Since changes in photosynthetic parameters are observed in the absence of visual injuries, these methodologies constitute fundamental tools to predict and evaluate the extent to which abiotic stresses damage photosynthesis.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Abiotic stress; Chlorophyll a fluorescence; climate change; Gas exchange; Oxidative stress; photosynthesis

Quercus ilex recruitment in a drier world: A multi-stage demographic approach - Pérez-Ramos, Ignacio M; Rodriguez-Calcerrada, Jesus; Ourcival, Jean M; Rambal, Serge (Perspectives in Plant Ecology, Evolution and Systematics, 2013)
There is a growing interest in understanding and forecasting the responses of plant communities to projected changes of environmental conditions. Multi-stage demographic approaches, where plant recruitment is explored across multiple and consecutive stages, are essential to obtain a whole overview of the consequences of increasing aridity on tree recruitment and forest dynamics, but they are still rarely used. In this study, we present the results of an experimental rainfall exclusion aimed to evaluate the impact of projected increasing drought on multiple stage-specific probabilities of recruitment in a key tree species typical of late-successional Mediterranean woodlands (Quercus ilex L.). We calibrated linear and nonlinear likelihood models for the different demographic processes and calculated overall probabilities of recruitment along a wide range of microhabitat conditions. Rainfall exclusion altered Q. ilex recruitment throughout ontogeny. Seed maturation, seedling emergence and survival and, to a lesser extent, post-dispersal seed survival were the most sensitive demographic processes to decreased rainfall. Interestingly, both the identity of the most critical stages for recruitment and their specific sensitivity to rainfall manipulation depended largely on the yearly pattern of precipitation. The microhabitat heterogeneity strongly determined the success of recruitment in the study species. The experimental increase in drought displaced the peak of maximum overall recruitment towards the low end of the light gradient, suggesting that the dependence on shrubs for an effective recruitment in Q. ilex could be intensified under future environmental scenarios. In terms of phenotypic plasticity, Q. ilex seedlings responded more strongly to light availability than to experimentally increased drought, which could reduce its ability to persist under on-going environmental conditions due to climate change. Results from this study provide a full picture of the ecological and functional consequences of the projected rainfall reduction on tree recruitment and forest dynamics in two years of contrasting precipitation.
Keywords: climate change; functional traits; Mediterranean woodland; Microhabitats; regeneration niche; seedling growth

Quercus ilex recruitment in a drier world: A multi-stage demographic approach - Pérez-Ramos, Ignacio M.; Rodriguez-Calcerrada, Jesus; Ourcival, Jean M.; Rambal, Serge (Perspectives in Plant Ecology, Evolution and Systematics, 2013)
There is a growing interest in understanding and forecasting the responses of plant communities to projected changes of environmental conditions. Multi-stage demographic approaches, where plant recruitment is explored across multiple and consecutive stages, are essential to obtain a whole overview of the consequences of increasing aridity on tree recruitment and forest dynamics, but they are still rarely used. In this study, we present the results of an experimental rainfall exclusion aimed to evaluate the impact of projected increasing drought on multiple stage-specific probabilities of recruitment in a key tree species typical of late-successional Mediterranean woodlands (Quercus ilex L.). We calibrated linear and nonlinear likelihood models for the different demographic processes and calculated overall probabilities of recruitment along a wide range of microhabitat conditions. Rainfall exclusion altered Q. ilex recruitment throughout ontogeny. Seed maturation, seedling emergence and survival and, to a lesser extent, post-dispersal seed survival were the most sensitive demographic processes to decreased rainfall. Interestingly, both the identity of the most critical stages for recruitment and their specific sensitivity to rainfall manipulation depended largely on the yearly pattern of precipitation. The microhabitat heterogeneity strongly determined the success of recruitment in the study species. The experimental increase in drought displaced the peak of maximum overall recruitment towards the low end of the light gradient, suggesting that the dependence on shrubs for an effective recruitment in Q. ilex could be intensified under future environmental scenarios. In terms of phenotypic plasticity, Q. ilex seedlings responded more strongly to light availability than to experimentally increased drought, which could reduce its ability to persist under on-going environmental conditions due to climate change. Results from this study provide a full picture of the ecological and functional consequences of the projected rainfall reduction on tree recruitment and forest dynamics in two years of contrasting precipitation.
The following values have no corresponding Zotero field: publisher: Elsevier GmbH.
Keywords: climate change; functional traits; Mediterranean woodland; Microhabitats; regeneration niche; seedling growth

Changes in soil organic carbon and climate change – Application of the RothC model in agro-silvo-pastoral Mediterranean systems - Francaviglia, Rosa; Coleman, Kevin; Whitmore, Andrew P.; Doro, Luca; Urracci, Giulia; Rubino, Mariateresa; Ledda, Luigi (Agricultural Systems, 2012)
Due to the complexity of soil organic carbon (SOC), models have proved very useful in helping to improve our understanding of the soil–plant–atmosphere system. In this study we used the Rothamsted carbon model (RothC), which considers the effect of climate (temperature, rainfall and evaporation), soil texture (clay content) and crop management on the decomposition processes, to predict changes in SOC under different land uses and the different climate that may occur in the future. SOC turnover was evaluated in land uses under different levels of agricultural intensiﬁcation. The agriculture of the study-area is mainly extensive and markedly agro-silvo-pastoral, and is typical of northeastern Sardinia (Italy) and similar areas of the Mediterranean basin. The following land uses were considered: vineyards, hay crops, pastures, semi-natural systems (formerly vineyards) and cork oak forests. Since the study-area is characterized by the same soil type (Haplic Endoleptic Cambisols, Dystric) derived from granitic rocks and potential native vegetation (Quercus suber L.), this was considered as the model baseline to study soil organic carbon dynamics. Climate change scenarios for 90 yr were generated from the baseline climate with two Global Climate Models: GISS (Goddard Institute of Space Studies, USA), and HadCM3 (Met Ofﬁce, Hadley Centre, UK), for two of the Intergovernmental Panel on Climate Change (IPCC) emission scenarios (SRES A2 and B2). Land uses at low cropping intensity were more efﬁcient than intensive agricultural systems in terms of SOC storage in the order: hay crop > pasture > cork oak forest > semi-natural systems. Land use change to vineyards decreased the carbon balance signiﬁcantly between 0.09 and 0.15 t C ha 1 yr 1 . However, former vineyards have almost recovered from soil disturbance following the establishment of the vineyards.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: C sequestration; climate change; CO2 emissions; Emission scenarios; land use; RothC

Climate change impacts on tree ranges: model intercomparison facilitates understanding and quantification of uncertainty - Cheaib, Alissar; Badeau, Vincent; Boe, Julien; Chuine, Isabelle; Delire, Christine; Dufrêne, Eric; François, Christophe; GRITTI, EMMANUEL S; Legay, Myriam; Pagé, Christian; Thuiller, Wilfried; Viovy, Nicolas; et al. (Ecology Letters, 2012)
Ecology Letters (2012) Abstract Model-based projections of shifts in tree species range due to climate change are becoming an important decision support tool for forest management. However, poorly evaluated sources of uncertainty require more scrutiny before relying heavily on models for decision-making. We evaluated uncertainty arising from differences in model formulations of tree response to climate change based on a rigorous intercomparison of projections of tree distributions in France. We compared eight models ranging from niche-based to process-based models. On average, models project large range contractions of temperate tree species in lowlands due to climate change. There was substantial disagreement between models for temperate broadleaf deciduous tree species, but differences in the capacity of models to account for rising CO2 impacts explained much of the disagreement. There was good quantitative agreement among models concerning the range contractions for Scots pine. For the dominant Mediterranean tree species, Holm oak, all models foresee substantial range expansion.
Keywords: climate change; Fagus sylvatica; France; Pinus sylvestris; Quercus ilex; Quercus petraea; Quercus robur; species range; vegetation model intercomparison

Evidence for plant traits driving specific drought resistance. A community field experiment - Matías, Luis; Quero, José Luis; Zamora, Regino; Castro, Jorge (Environmental and Experimental Botany, 2012)
Drought is known to be a major bottleneck for woody-community recruitment. The species-speciﬁc resistance to drought and factors involved in its variation are of special interest to forecast community fate. We performed an experiment under natural ﬁeld conditions from winter 2006 to end summer 2008 to investigate the structural responses of woody saplings to nine combinations of light (three habitats differing in plant cover:forest, shrubland, and open) andwater (three climate scenarios: drier, current and wetter summers). Our working hypothesis is that plant strategies to cope with drought are determined by habitat characteristics and/or variation of plant traits, and that these different strategies may determine community composition and dynamics. Eight woody species with different life forms and successional stages (trees, mid-successional shrubs, and pioneer shrubs) were selected for the comparison, including therefore species representative of the entire woody community. We explored drought resistance at the population level (DS), the relations of the different morphological traits to DS, and the potential importance for plants of inter-speciﬁc trade-offs. DS ranged from 0% to 99% for the different species, depending on the habitat. Some structural traits were found to be related to DS: positively with total biomass and leaf mass ratio (LMR) and negatively with leaf area-root mass ratio (LARMR). Contrary to previous studies, the present work revealed no evidence of trade-offs, such as survival in forest vs. growth in open, or growth in forest vs. growth in open. Accordingly, some species with low DS values (Acer opalus and Pinus sylvestris) would be threatened under the future climate conditions, while species having structural characteristics to increase their resistance under expected dry years in coming decades (i.e., high LMR and total biomass or low LARMR, such as Quercus ilex and the shrub Cytisus scoparius) might enhance their recruitment probabilities. Thus, species-speciﬁc plant traits, and their effect on DS, may ﬁlter future community assemblages.
Keywords: biomass allocation; climate change; Mediterranean; Structural traits; Survival; Trade-off

Holocene vegetation and fire dynamics in the supra-mediterranean belt of the Nebrodi Mountains (Sicily, Italy) - Bisculm, Martina; Colombaroli, Daniele; Vescovi, Elisa; van Leeuwen, Jacqueline F. N.; Henne, Paul D.; Rothen, Julian; Procacci, Giovanni; Pasta, Salvatore; La Mantia, Tommaso; Tinner, Willy (Journal of Quaternary Science, 2012)
High-resolution pollen, macrofossil and charcoal data, combined with accelerator mass spectrometry 14C dating and multivariate analysis, were used to reconstruct Holocene vegetation and fire dynamics at Urio Quattrocchi, a small lake in the supra-mediterranean belt in the Nebrodi Mountains of Sicily (Italy). The data suggest that after 10 000 cal a BP increasing moisture availability supported closed forests with deciduous (Quercus cerris, Fagus sylvatica and Fraxinus spp.) and evergreen (Quercus ilex) species. Species-rich closed forest persisted until 6850 cal a BP, when Neolithic activities caused a forest decline and affected plant diversity. Secondary forest with abundant Ilex aquifolium recovered between 6650 and 6000 cal a BP, indicating moist conditions. From 5000 cal a BP, agriculture and pastoralism led to the currently fragmented landscape with sparse deciduous forests (Quercus cerris). The study suggests that evergreen broadleaved species were more important at elevations above 1000 m a.s.l. before ca. 5000 cal a BP than subsequently, which might reflect less human impact or warmer-than-today climatic conditions between 10 000 and 5000 cal a BP. Despite land use since Neolithic times, deciduous supra-mediterranean forests were never completely displaced from the Nebrodi Mountains, because of favourable moist conditions that persisted throughout the Holocene. Reconstructed vegetation dynamics document the absence of any pronounced mid- or late-Holocene ‘aridification’ trend at the site, an issue which is controversially debated in Italy and the Mediterranean region. Copyright © 2012 John Wiley & Sons, Ltd.
The following values have no corresponding Zotero field: publisher: John Wiley & Sons, Ltd.
Keywords: climate change; human impact; Ilex aquifolium; macrofossils; pollen; Quercus ilex

Landscape planning for the future: using fossil records to independently validate bioclimatic envelope models for economically valuable tree species in Europe - Macias-Fauria, Marc; Willis, Katherine J (Global Ecology and Biogeography, 2012)
Aim Bioclimatic envelope models (BEMs) for seven economically important tree species in Europe were independently validated using a hindcasting approach and fossil pollen records spanning the last 1000 years, including the Medieval Warm Period (MWP), the Little Ice Age (LIA) and the 20th century (PRES). The aim was to determine the accuracy of combining BEMs and palaeoecological data to predict continental-scale changes in distribution, and the availability of fossil data to hindcast economically important species. Location Europe, 11 °W–33 °E, 33–72 °N. Methods Eight types of BEMs were implemented in this study, covering most state-of-the-art modelling techniques. Present and palaeoclimatic data were obtained from the atmosphere–ocean global circulation model ECHO-G. The last millennium was divided into three climatically distinct periods: the MWP (ad 900–1300), the LIA (ad 1600–1850) and PRES (ad 1900–2000). Models were calibrated for each period and validated with climatic and pollen data from the remaining periods. Successfully validated models were projected onto a 1° European grid. Results BEMs were successfully validated with independent data. The average area under the curve statistic showed strong model performance, indicating: (1) the strength of BEMs for modelling current and future distributions and, (2) the potential of fossil pollen records to undertake these approaches. European-scale 1°- gridded maps of probability of occurrence largely agreed with observed 20th-century distributions for most taxa, allowing the construction of past modelled species distributions. Main conclusions Results suggest a high potential for BEMs to be used to model future species distributions, and highlight the importance of palaeoecological data to independently validate these models, taking into account the scales at which these data operate. Although valid, BEMs showed poorer performance with heavily managed species and/or those growing in heterogeneous terrain or with discontinuous distributions. The last millennium in Europe was characterized by an increase in woody crop species and a decline of forest species, suggesting increasing land use by humans.
Keywords: Bioclimatic envelope models; climate change; conservation planning; EUROPE; Little Ice Age; Medieval Warm Period; species distribution models; woody species

The likely impact of climate change on the biodiversity of Italian forests - Borghetti, M.; La Mantia, T.; Menozzi, P.; Piotti, a (Forest@ - Rivista di Selvicoltura ed Ecologia Forestale, 2012)
Keywords: 2012; 245-250; 9; Adaptation; biodiversità delle foreste italiane; Biodiversity; borghetti m; citation; climate change; climatico sulla; contents; FOREST; http; impact; it; Italy; la mantia t; menozzi p; online 2012-11-19; piotti a; probabili impatti del cambiamento; sisef; url; www

Litter production in Holm oak trees subjected to different pruning intensities in Mediterranean dehesas - Andivia, Enrique; VÁZQUEZ-PIQUÉ, JAVIER; FERNÁNDEZ, MANUEL; Alejano, Reyes (Agroforestry systems, 2012)
Litterfall is a key process in forests which is sensitive to climatic conditions like precipitation and temperature, and management practices. Therefore, knowledge about litterfall patterns and its associated variables is important for the conservation of Mediterranean ecosystems under conditions of climate change. We aimed to quantify the temporal pattern of litterfall and to investigate the inﬂuence of abiotic variables and pruning on litter production. Litterfall was collected at monthly intervals for 2 years in trees subjected to different pruning intensities in two locations. The effect of pruning, abiotic variables and tree size on litter production was analyzed using a mathematical model. Leaf fall was strongly seasonal with a peak occurring in the wettest month of the year in this area. The variability in leaf fall was mainly related to rainfall and soil water in 2 years and locations. Pruning reduced the amount of litter production during the ﬁrst year following this practice, and might have negative effect on soil fertility and crop productivity in dehesas ecosystems.
Keywords: á agroforestry systems; á litterfall á; agroforestry systems; climate change; climate change á management; litterfall; management; pruning; Quercus ilex; quercus ilex á pruning

A phytoclimatic-based indicator for assessing the inherent responsitivity of the European forests to climate change - García-López, Javier M.; Allué, Carmen (Ecological Indicators, 2012)
We assess the potential inherent responsitivity of the European forests to climate change, as a measure of the degree to which a forest ecosystem is responsive to a climatic stimulus, through an indicator that combines the concepts of resilience and plasticity without involving exposure. The derivatives of two phytoclimatic functions of resilience and plasticity adjusted for 12 climatic variables and 25 European forest types allow evaluating the responsitivity amount and sign of these forest types to likely situations of increased temperature and decreased precipitation. The results show a clear contrast between central and northern European countries. The highest values of positive responsitivity are found in the Scandinavian countries, as well as in the high mountain ranges, while the most negative values are found in the areas of southern Europe located around the Mediterranean Sea. Thus, climate change will tend to have the highest potential beneﬁcial effects on the boreal forests and the most adverse on the Mediterranean ones (particularly on Thermo-Mediterranean forests). A total of 17% of forest lands covered by this study have negative responsitivity to climate change, being the mean value of the indicator negative for Italy, Spain, Greece, Malta and Portugal. Finland and Sweden are the countries with the greatest favorable potentialities facing climate change. Our results suggest that the inherent responsitivity of Mediterranean forests is mainly driven by the summer drought while in boreal forests the key factors are the low temperatures and the short growing season.
Keywords: climate change; European forests; Plasticity; resilience; vulnerability

Spatio-temporal patterns of Holocene environmental change in southern Sicily - Calò, Camilla; Henne, Paul D.; Curry, Brandon; Magny, Michel; Vescovi, Elisa; La Mantia, Tommaso; Pasta, Salvatore; Vannière, Boris; Tinner, Willy (Palaeogeography, Palaeoclimatology, Palaeoecology, 2012)
Few examples of natural forest remain near the Mediterranean coast. Therefore, it is difﬁcult to study how coastal forests respond to climatic change or their resilience to human impact. We developed new sedimentary record of Holocene vegetation and ﬁre history at Lago Preola, a coastal lake in southwestern Sicily (Italy). In order to verify the existence of forest at large scale on the coast, we compare pollen from Lago Preola, a medium-sized lake (33 ha), to Gorgo Basso, a small lake (3 ha) located nearby with the aim of separating local from extra-local vegetation dynamics through time using pollen percentages and inﬂux. We then compare Lago Preola pollen to the record from Biviere di Gela, a large lagoon (120 ha) situated 160 km to the east in southern Sicily, to examine differences in vegetation dynamics between the two coastal areas during the Holocene. Lake-level reconstructions and ostracode analyses from Lago Preola provide vegetation-independent evidence of climate change, and help to disentangle human and climatic impacts on vegetation. Pollen data indicate Pistacia-dominated shrublands replaced open grasslands in the region surrounding Lago Preola by 9500 cal yr BP. This change coincided with rising lake levels and the development of an ostracode fauna typical of fresh waters. Evergreen forest dominated by Quercus ilex and Olea europaea started to expand by 7000 cal BP and consolidated at 6500 cal yr BP, when lake levels were near their Holocene high. Similarities between pollen from Lago Preola and Gorgo Basso demonstrate that forest was the dominant vegetation type in coastal Sicily during the middle Holocene at both regional and local scales, and even developed in the drier climatic setting around Biviere di Gela. Lake levels fell at Lago Preola after 7000 cal yr BP, with a strong decline accompanied by increasing salinity after 4500 cal yr BP. However, no transition in vegetation matched these inferred hydrological changes. Instead, forests persisted in the surrounding region until 2200 cal BP when human disturbance intensiﬁed. We propose that different climatic factors control lake levels and vegetation in coastal Mediterranean ecosystems. Whereas lake levels are most sensitive to the abundance of winter precipitation, coastal forests depend on spring precipitation and are limited by the length of summer drought. Moisture availability remained suitable for evergreen forests in coastal Sicily during the late Holocene, and humans, not a drier climate drove the regional forest decline.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: climate change; Holocene; Mediterranean; paleoecology; Paleohydrology; Sicily

Sporadic rainy events are more critical than increasing of drought intensity for woody species recruitment in a Mediterranean community. - Matías, Luis; Zamora, Regino; Castro, Jorge (Oecologia, 2012)
The understanding of the impact of extreme climatic events under a global climate change scenario is crucial for the accurate forecast of future plant community dynamics. We have experimentally assessed the effect of drier and wetter summer conditions on the recruitment probabilities and the growth of seedlings from eight woody species representative of the most important functional groups in the community, pioneer shrubs, mid-successional shrubs and trees, across the main habitats in the study area (open habitat, shrubland, and forest). Our hypothesis proposes that wet summer conditions would represent a good opportunity for tree species regeneration, enhancing both forest maintenance and expansion. A drier summer scenario, on the other hand, would limit forest regeneration, and probably hinder the colonization of nearby habitats. We found a habitat effect on the emergence, survival, and final biomass, whereas different climate scenarios affected seedling survival and biomass. A wet summer boosted growth and survival, whereas greater drought reduced survival only in some cases. These results were modulated by the habitat type. Overall, shrub species presented higher survival and growth and were less affected by more severe drought, whereas some tree species proved to be extremely dependent on wet summer conditions. We conclude that the reduction in frequency of wet summers predicted for the coming decades in Mediterranean areas will have greater consequences for species recruitment than will increased drought. The different response of the species from the various functional groups has the potential to alter the composition and dominance of future plant communities.
Keywords: Angiosperms; Angiosperms: growth & development; climate change; Droughts; Ecosystem; Mediterranean Region; Rain; rainfall variability; Recruitment; Seedling; Seedling: growth & development; Spain; summer drought; Vegetation dynamics

Variability of relationships between soil organic carbon and some soil properties in Mediterranean rangelands under different climatic conditions (South of Spain) - Ruiz Sinoga, Jose Damian; Pariente, Sarah; Diaz, Asuncion Romero; Martinez Murillo, Juan Francisco (Catena, 2012)
Changes in land use and vegetation cover affect various soil properties, including the soil organic carbon (SOC) pool and the transfer of atmospheric CO2 to terrestrial landscapes. In natural or quasi-natural conditions a reduction in biomass increases the risk of erosion, and can reduce the stored soil organic matter content. This can cause (i) consolidation of low levels of organic carbon stored in the soil; (ii) reduction in the levels of organic carbon because of the onset of erosion processes; and (iii) differing rates of recovery of the soil in response to environmental factors including precipitation, which is a principal agent of indirect recharge of soil organic matter. Few comparable studies have analyzed the reduction of SOC because of erosion, and assessed how this contributes to the loss of soil as vegetation cover decreases. This is particularly the case in semiarid Mediterranean environments, where erosion is one of the main causes of soil degradation. This study presents the results of an experiment carried out along a pluviometric gradient from humid to semiarid Mediterranean conditions, in southern Spain. The study involved two soil depths at ﬁve ﬁeld sites having similar lithology, slope and aspect, but differ in vegetation cover and composition related to their location along the gradient. We used soil cation exchange capacity (CEC) as an indicator of soil degradation. The results showed that: a) SOC decreased with decreasing rainfall; b) SOC is greater at the soil surface than at depth; c) CEC is a good indicator of the degradation of soil surface formations, as it is directly related to the SOC storage capacity; and d) the so-called “Mediterranean mountain” landscape, with sparse and mixed vegetation composed of scrubland and woodland species, is a good organic carbon sink with direct implications in relation to climate change.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Cation exchange capacity; climate change; desertification; Pluviometric gradient; Soil degradation; Soil organic carbon

Is cellular automata algorithm able to predict the future dynamical shifts of tree species in Italy under climate change scenarios? A methodological approach - Di Traglia, Mario; Attorre, Fabio; Francesconi, Fabio; Valenti, Roberto; Vitale, Marcello (Ecological Modelling, 2011)
In this paper is presented a methodological approach which integrates statistic modelling and 2-D cellular automata (CA) in order to describe tree species shifts responding to the climate changes foreseen for Italy in the 21st century. Five Italian tree species populations of Abies alba, Pinus sylvestris, Fagus sylvatica, Acer campestris and Quercus suber and their actual potential distributions (PDs) – represented by Importance Value (IV), have been considered. Environmental and climatic relationships have been modelled through application of a new statistical methodology called extreme discretization, where the PD of a species was considered as a random ﬁeld. The IV-based PD has been spatialized through a probability function (A,S), which represented the spatio-temporal relationships between IV values and climatic (A) and geomorphological (S) variables. For each tree species = (A,S) has been estimated and inserted as rule in the 2-D cellular automata. The latter, acting by a Moore neighbouring, took in consideration also the suitability map for tree species, which has been obtained by land cover map. Two time frames (2050 and 2080) and two climatic scenarios (A2 and B1) have been considered. Results described a general reduction of the IV values and their distribution for A. alba, P. sylvestris and F. sylvatica, in both climatic scenarios, whereas an increase of IVs and distribution for Q. suber and only a slight increment of distribution for A. campestris was mainly observed under the B1 scenario, but not for the more limiting A2 scenario. Convergent results have been obtained with respect to other simulation systems concerning the shift of tree species responding to different climatic change scenarios but lacking of the description of dynamical paths. Our approach seems natural and practical to describe such phenomena. The transition rules for the CA and the parameters taken into account for the construction of the probabilistic models can be surely improved to obtain a more realistic pattern of tree species shifts. Future efforts should be made to take in account the inter-speciﬁc relationships inside the Italian forest ecosystems, in order to also consider the competiveness for resources that exert some effects on the plant distribution both in time and space.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: 2-d cellular automata; climate change; Importance Value; Logistic analysis; Mediterranean basin; Potential tree species shift

Changes in land cover and vegetation carbon stocks in Andalusia, Southern Spain (1956-2007). - Muñoz-Rojas, M; De la Rosa, D; Zavala, L M; JORDÁN, A; Anaya-Romero, M (The Science of the total environment, 2011)
Land use has significantly changed during the recent decades at global and local scale, while the importance of ecosystems as sources/sinks of C has been highlighted, emphasizing the global impact of land use changes. Land use changes can increase C loss rates which are extremely difficult to reverse, in the short term, opposite to organic carbon (OC) which accumulates in soil in the long-term. The aim of this research is to improve and test methodologies to assess land cover change (LCC) dynamics and temporal and spatial variability in C stored in vegetation at a wide scale. LCCs between 1956 and 2007 in Andalusia (Southern Spain) were selected for this pilot study, assessed by comparison of spatial data from 1956 to 2007 and were reclassified following land cover flows (LCFs) reported in major areas in Europe. Carbon vegetation densities were related to land cover, and C vegetation stocks for 1956 and 2007 were calculated by multiplying C density for each land cover class with land cover areas. The study area has supported important changes during the studied period with significant consequences for vegetation C stocks, mainly due to afforestation and intensification of agriculture, resulting in a total vegetation C stock of 156.08Tg in 2007, with an increase of 17.24Tg since 1956. This study demonstrates the importance of LCC for C sequestration in vegetation from Mediterranean areas, highlighting possible directions for management policies in order to mitigate climate change as well as promoting land conservation. The methodologies and information generated in this project will be a useful basis for designing land management strategies helpful for decision makers.
Keywords: Agriculture; Agriculture: statistics & numerical data; Carbon; Carbon Sequestration; Carbon: analysis; Carbon: metabolism; Cities; Cities: statistics & numerical data; climate change; Conservation of Natural Resources; CORINE Land Cover; Environment; Environmental Monitoring; Land use planning; Plant Development; Plants; Plants: chemistry; Plants: metabolism; Soil Pollutants; Soil Pollutants: analysis; Soil Pollutants: metabolism; Spain; Sustainable land management

Chlorophyll fluorescence responses to temperature and water availability in two co-dominant Mediterranean shrub and tree species in a long-term field experiment simulating climate change - Ogaya, Romà; Penuelas, Josep; Asensio, Dolores; Llusia, Joan (Environmental and Experimental Botany, 2011)
A rain exclusion experiment simulating drought conditions expected in Mediterranean areas for the following decades (15% decrease in soil moisture) is being conducted since 1999 in a Mediterranean holm oak forest to study its response to the forecasted climatic changes for the coming decades. The maximum PSII quantum yield of primary photochemistry (Fv/Fm) was measured in Quercus ilex, and Phillyrea latifolia, the co-dominant species of the studied forest, from 1999 to 2009 in four plots: two of them were control plots and the other two plots received the rain exclusion treatment. In both species, the Fv/Fm values were highly dependent on air temperatures, and in a second term, in water availability. P. latifolia was the species with the larger decrease in Fv/Fm values induced by low air temperatures, while in hot seasons, the Fv/Fm values in P. latifolia were even higher than in Q. ilex. Rainfall exclusion decrease Fv/Fm values signiﬁcantly only in few monitoring dates. The most drought resistant species P. latifolia was more affected by the experimental rainfall exclusion than Q. ilex that instead lost number of leaves per tree. There was a synergic effect of drought stress and winter cold in P. latifolia not observed in Q. ilex, but a more conservative strategy in P. latifolia maintaining leaves with a down-regulation of the linear photosynthetic electron transport. These results indicate that, although other physiological and reproductive strategies at whole plant level must be also taken into account, the warmer and drier environment expected for the following decades could favour the species more sensitive to cold and more resistant to drought, the shrub P. latifolia, in detriment of the tree Q. ilex as already observed in the ﬁeld after severe heat-drought episodes.
Keywords: Chlorophyll ﬂuorescence; climate change; Cold; Drought; evergreen leaves; Fv/Fm; Heat; mediterranean forest; phillyrea latifolia; Quercus ilex

Disentangling the relative importance of climate, size and competition on tree growth in Iberian forests: implications for forest management under global change - Gómez-Aparicio, LORENA; GARCÍA-VALDÉS, Raúl; Ruíz-Benito, PALOMA; Zavala, MIGUEL a (Global Change Biology, 2011)
Most large-scale multispecies studies of tree growth have been conducted in tropical and cool temperate forests, whereas Mediterranean water-limited ecosystems have received much less attention. This limits our understanding of how growth of coexisting tree species varies along environmental gradients in these forests, and the implications for species interactions and community assembly under current and future climatic conditions. Here, we quantify the absolute effect and relative importance of climate, tree size and competition as determinants of tree growth patterns in Iberian forests, and explore interspecific differences in the two components of competitive ability (competitive response and effect) along climatic and size gradients. Spatially explicit neighborhood models were developed to predict tree growth for the 15 most abundant Iberian tree species using permanent-plot data from the Spanish Second and Third National Forest Inventory (IFN). Our neighborhood analyses showed a climatic and size effect on tree growth, but also revealed that competition from neighbors has a comparatively much larger impact on growth in Iberian forests. Moreover, the sensitivity to competition (i.e. competitive response) of target trees varied markedly along climatic gradients causing significant rank reversals in species performance, particularly under xeric conditions. We also found compelling evidence for strong species-specific competitive effects in these forests. Altogether, these results constitute critical new information which not only furthers our understanding of important theoretical questions about the assembly of Mediterranean forests, but will also be of help in developing new guidelines for adapting forests in this climatic boundary to global change. If we consider the climatic gradients of this study as a surrogate for future climatic conditions, then we should expect absolute growth rates to decrease and sensitivity to competition to increase in most forests of the Iberian Peninsula (in all but the northern Atlantic forests), making these management considerations even more important in the future.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: 2 march 2011; climate change; competitive effect; competitive response; Forests; iberian peninsula; march 2011 and accepted; maximum likelihood; Mediterranean; Mediterranean forests; neighhorbood models; received 21 october 2010; revised version received 1; species rank reversals; tree coexistence

Increasing Drought Sensitivity and Decline of Atlas Cedar (Cedrus atlantica) in the Moroccan Middle Atlas Forests - Linares, Juan C; Taiqui, Lahcen; Julio Camarero, Jesus (FORESTS, 2011)
An understanding of the interactions between climate change and forest structure on tree growth are needed for decision making in forest conservation and management. In this paper, we investigated the relative contribution of tree features and stand structure on Atlas cedar (Cedrus atlantica) radial growth in forests that have experienced heavy grazing and logging in the past. Dendrochronological methods were applied to quantify patterns in basal-area increment and drought sensitivity of Atlas cedar in the Middle Atlas, northern Morocco. We estimated the tree-to-tree competition intensity and quantified the structure in Atlas cedar stands with contrasting tree density, age, and decline symptoms. The relative contribution of tree age and size and stand structure to Atlas cedar growth decline was estimated by variance partitioning using partial-redundancy analyses. Recurrent drought events and temperature increases have been identified from local climate records since the 1970s. We detected consistent growth declines and increased drought sensitivity in Atlas cedar across all sites since the early 1980s. Specifically, we determined that previous growth rates and tree age were the strongest tree features, while Quercus rotundifolia basal area was the strongest stand structure measure related to Atlas cedar decline. As a result, we suggest that Atlas cedar forests that have experienced severe drought in combination with grazing and logging may be in the process of shifting dominance toward more drought-tolerant species such as Q. rotundifolia.
Keywords: basal area increment; Cedrus atlantica; climate change; Dendroecology; Drought; Forest structure; partial redundancy analysis

Modelling phytoclimatic versatility as a large scale indicator of adaptive capacity to climate change in forest ecosystems - García-López, Javier M.; Allué, Carmen (Ecological Modelling, 2011)
CLIMPAIR is a new phytoclimatic model, correlative and niche-based, which simultaneously assesses non-linear, non-statistical and dual measurements of proximity/potentiality of a site with respect to a number of climatic ranges of species, deﬁned by convex hulls, within a suitability space. This set of phytoclimatic distances makes it possible to evaluate the degree to which each species is suitable for that site. Considering not only the number of species compatible (expected species richness), but also all those compatible covers presenting a high level of suitability evenness and ﬁnally applying an indicator derived from Shannon’s classic entropy index to the set of standardized phytoclimatic coordinates in the suitability hyperspace, we can evaluate the phytoclimatic entropy which may be considered as a means of estimating the phytoclimatic versatility of the site. A site with high phytoclimatic entropy would promise versatile future behaviour, characterized by a wide range of possibilities of adaptation to climate change, and hence versatility can be used as an index of resilience and ability of a forest ecosystem to adapt to climate change. The model has been applied to peninsular Spain for 18 forest tree species and 12 climatic variables between the current mean climate (period 1951–1999) and a future climatic scenario (period 2040–2069). The results generally point to a signiﬁcant decrease in the versatility of forest tree formations in the area studied, which is not homogeneous owing to a dual altitudinal/latitudinal decoupling. The decrease in versatility is greater in Mediterranean biogeographical areas than in Euro-Siberian ones, where in some cases it actually increases. In altitudinal terms, areas at elevations of less than 1500 m tend to become less versatile than areas situated at higher elevations, where versatility increases partly as a result of enrichment of alpine conifer forests with broadleaf species.
Keywords: Adaptive capacity; climate change; resilience; suitability; Tree species diversity; Versatility; vulnerability

Phenological trends in southern Spain: A response to climate change - García-Mozo, H.; Mestre, a; Galan, C. (Agricultural and Forest Meteorology, 2010)
The impact of climate change, and particularly of climate warming, is being tracked in many physical and biological systems. Plant phenology is seen as one of the most important bio-indicators, since trends can provide considerable temporal and spatial information regarding ongoing changes. Analyses performed at six sites in southern Spain from 1986 to the present have focused on vegetative and overall reproductive phenology in Olea europaea L., and Vitis vinifera L. and in various species of Quercus spp. and Poaceae. Early results suggest that trends in ﬂowering patterns derived from ﬁeld phenological observations were similar to trends in aerobiological data for most study species, and indicate a trend towards earlier foliation, ﬂowering and fruit ripening. This advance is more evident in arboreal than in herbaceous species. Statistical analysis showed temperature increase was the major factor affecting earlier foliation, ﬂowering and fruit ripening, as well as prompting delayed leaf fall. Herbaceous species were more affected than trees by changes in rainfall records
Keywords: Aerobiology; climate change; Phenology; pollen

Biogenic volatile organic compounds in the Earth system - Laothawornkitkul, Jullada; Taylor, Jane E; Paul, Nigel D; Hewitt, C Nicholas (New Phytologist, 2009)
Contents * Summary 27 * I. Introduction 27 * II. Regulation of BVOC emission 30 * III. Roles of BVOCs in the Earth system 32 * IV. BVOCs in a changing global environment 36 * V. Synthesis 44 * Acknowledgements 44 * References 44 Summary Biogenic volatile organic compounds produced by plants are involved in plant growth, development, reproduction and defence. They also function as communication media within plant communities, between plants and between plants and insects. Because of the high chemical reactivity of many of these compounds, coupled with their large mass emission rates from vegetation into the atmosphere, they have significant effects on the chemical composition and physical characteristics of the atmosphere. Hence, biogenic volatile organic compounds mediate the relationship between the biosphere and the atmosphere. Alteration of this relationship by anthropogenically driven changes to the environment, including global climate change, may perturb these interactions and may lead to adverse and hard-to-predict consequences for the Earth system.
Keywords: atmospheric chemistry; biogenic volatile organic compounds (BVOCs); climate change; Global warming; plant defence; plant volatiles; tritrophic interaction

Differences between tree species seedling and adult altitudinal distribution in mountain forests during the recent warm period (1986–2006) - Lenoir, Jonathan; Gégout, Jean-Claude; Pierrat, Jean-Claude; Bontemps, Jean-Daniel; Dhôte, Jean-François (Ecography, 2009)
Spatial fingerprints of climate change on tree species distribution are usually detected at latitudinal or altitudinal extremes (arctic or alpine tree line), where temperatures play a key role in tree species distribution. However, early detection of recent climate change effects on tree species distribution across the overall temperature gradient remains poorly explored. Within French mountain forests, we investigated altitudinal distribution differences between seedling (≤50 cm tall and >1 yr old) and adult (>8 m tall) life stages for 17 European tree taxa, encompassing the entire forest elevation range from lowlands to the subalpine vegetation belt (50–2250 m a.s.l.) and spanning the latitudinal gradient from northern temperate to southern Mediterranean forests. We simultaneously identified seedlings and adults within the same vegetation plots. These twin observations gave us the equivalent of exactly paired plots in space with seedlings reflecting a response to the studied warm period (1986–2006) and adults reflecting a response to a former and cooler period. For 13 out of 17 species, records of the mean altitude of presence at the seedling life stage are higher than that at the adult life stage. The low altitudinal distribution limit of occurrences at the seedling life stage is, on average, 29 m higher than that at the adult life stage which is significant. The high altitudinal distribution limit also shows a similar trend but which is not significant. Complementary analyses using modelling techniques and focusing on the optimum elevation (i.e. the central position inside distribution ranges) have confirmed differences between life stages altitudinal distribution. Seedlings optima are mostly higher than adults optimum, reaching, on average, a 69 m gap. This overall trend showing higher altitudinal distribution at the seedling life stage in comparison to the adult one suggests a main driver of change highly related to elevation, such as climate warming that occurs during the studied period. Other drivers of change that could play an important role across elevation or act at more specific scales are also discussed as potential contributors to explain our results.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Altitudinal distribution; climate change; seedlings (PG); Tree species distribution

Growth response of mixed mediterranean oak coppices to rainfall reduction - Cotillas, Miriam; Sabaté, Santi; Gracia, Carlos; Espelta, Josep Mª (Forest Ecology and Management, 2009)
Climate change is one of the major challenges for ecosystem conservation. One of the most vulnerable areas to climate change is the Mediterranean Basin which is expected to suffer important changes in temperature and precipitation in the next few decades, leading to a warmer and dryer climate. Therefore, it is necessary to determine species-speciﬁc responses to increased drought to predict possible future changes in the structure and composition of Mediterranean forests, as well as to identify appropriate management strategies to mitigate these effects. The main aim of this study has been to experimentally simulate the effects of a 15% reduction in annual rainfall on the survival and growth of two co-occurring Mediterranean oaks with contrasting leafhabit (the evergreen Quercus ilex spp. ilex and the winter-deciduous Quercus cerrioides) and, to assess whether traditional selective thinning carried out in these mixed oak coppices (i.e. selection of one to few stems per stump) can modify the consequences of rainfall reduction. Soil moisture decreased under the rainfall reduction level while it increased in the thinned plots. Reduced rainfall did not inﬂuence tree mortality, but did lead to species-speciﬁc effects on height growth: no changes were observed in Q. ilex while height growth rate of Q. cerrioides decreased (c.a. 20%). Selective thinning improved tree growth (c.a. 50%) in stands both under natural and, and to a lesser extent, under reduced rainfall conditions. Nevertheless, the positive effects of thinning rapidly declined during our three years experiment, probably because the vigorous resprouting of thinned stumps. Our results show that the forecasted reduction in annual rainfall for the Western Mediterranean Basin can constrain the growth of some deciduous oaks in mixed oak coppices. Traditional selective thinning can increase soil moisture and encourage tree growth, thus partially mitigating this effect. However, the transient results observed in this experiment suggest the need to reconsider the intensity and the frequency of this traditional management practice in light of new climatic scenarios
Keywords: climate change; Drought; Forest management; Quercus cerrioides; Quercus ilex; resprouting

Growth response of mixed mediterranean oak coppices to rainfall reduction - Cotillas, Miriam; Sabaté, Santi; Gracia, Carlos; Espelta, Josep Mª (Forest Ecology and Management, 2009)
Climate change is one of the major challenges for ecosystem conservation. One of the most vulnerable areas to climate change is the Mediterranean Basin which is expected to suffer important changes in temperature and precipitation in the next few decades, leading to a warmer and dryer climate. Therefore, it is necessary to determine species-speciﬁc responses to increased drought to predict possible future changes in the structure and composition of Mediterranean forests, as well as to identify appropriate management strategies to mitigate these effects. The main aim of this study has been to experimentally simulate the effects of a 15% reduction in annual rainfall on the survival and growth of two co-occurring Mediterranean oaks with contrasting leafhabit (the evergreen Quercus ilex spp. ilex and the winter-deciduous Quercus cerrioides) and, to assess whether traditional selective thinning carried out in these mixed oak coppices (i.e. selection of one to few stems per stump) can modify the consequences of rainfall reduction. Soil moisture decreased under the rainfall reduction level while it increased in the thinned plots. Reduced rainfall did not inﬂuence tree mortality, but did lead to species-speciﬁc effects on height growth: no changes were observed in Q. ilex while height growth rate of Q. cerrioides decreased (c.a. 20%). Selective thinning improved tree growth (c.a. 50%) in stands both under natural and, and to a lesser extent, under reduced rainfall conditions. Nevertheless, the positive effects of thinning rapidly declined during our three years experiment, probably because the vigorous resprouting of thinned stumps. Our results show that the forecasted reduction in annual rainfall for the Western Mediterranean Basin can constrain the growth of some deciduous oaks in mixed oak coppices. Traditional selective thinning can increase soil moisture and encourage tree growth, thus partially mitigating this effect. However, the transient results observed in this experiment suggest the need to reconsider the intensity and the frequency of this traditional management practice in light of new climatic scenarios
Keywords: climate change; Drought; Forest management; Quercus cerrioides; Quercus ilex; resprouting

Fire-vegetation interactions during the Mesolithic-Neolithic transition at Lago dell'Accesa, Tuscany, Italy - Colombaroli, Daniele; Vannière, Boris; Emmanuel, Chapron; Magny, Michel; Tinner, Willy (HOLOCENE, 2008)
A new core from the centre of Lago dell'Accesa (Tuscany, Italy) was sampled for pollen and charcoal analyses to provide a high-resolution sequence from 8400 to 7000 cal. yr BP. We combined series of microscopic charcoal, macroscopic charcoal and pollen to address the response of vegetation to fire at different spatial scales. Before 7900 cal. yr BP, broadleaved evergreen forests of Quercus ilex were the most important vegetational type in the area of Lago dell'Accesa. The subsequent decline of Q. ilex occurred when human-induced fires increased at the Mesolithic/Neolithic transition (c. 8000 cal. yr BP). Cross-correlation analyses show that fire was a key factor for vegetational change. Higher fire incidence affected the forest composition, converting evergreen forests to high-diversity open, partly deciduous forests and shrubby communities. The correlation is more pronounced at a local scale (macroscopic charcoal), whereas at a regional scale (microscopic charcoal) the vegetation followed the fire intervals with a more marked time lag (10-100 years). Climatic change, such as wetter periods inferred from lake levels, may have directly influenced the vegetational change, exacerbating the effect of human impact. Our study suggests that the disruption of evergreen broadleaved forests occurred when mean fire interval reached values as high as those of today's highly disturbed Mediterranean ecosystems. Hence broadleaved evergreen forests may not be as fire-resilient as assumed according to modern ecological paradigms. In view of the projected increase in fire frequency as a consequence of global warming, the present relict forests of Quercus ilex will be strongly affected.
The following values have no corresponding Zotero field: pub-location: 1 OLIVERS YARD, 55 CITY ROAD, LONDON EC1Y 1SP, ENGLAND publisher: SAGE PUBLICATIONS LTD
Keywords: climate change; Fire ecology; Fire history; Holocene; Italy; macroscopic charcoal; Mediterranean vegetation; mesolithic; microscopic charcoal; Neolithic; Quercus ilex; tuscany

Fire-vegetation interactions during the Mesolithic-Neolithic transition at Lago dell'Accesa, Tuscany, Italy - Colombaroli, Daniele; Vannière, Boris; Emmanuel, Chapron; Magny, Michel; Tinner, Willy (HOLOCENE, 2008)
A new core from the centre of Lago dell'Accesa (Tuscany, Italy) was sampled for pollen and charcoal analyses to provide a high-resolution sequence from 8400 to 7000 cal. yr BP. We combined series of microscopic charcoal, macroscopic charcoal and pollen to address the response of vegetation to fire at different spatial scales. Before 7900 cal. yr BP, broadleaved evergreen forests of Quercus ilex were the most important vegetational type in the area of Lago dell'Accesa. The subsequent decline of Q. ilex occurred when human-induced fires increased at the Mesolithic/Neolithic transition (c. 8000 cal. yr BP). Cross-correlation analyses show that fire was a key factor for vegetational change. Higher fire incidence affected the forest composition, converting evergreen forests to high-diversity open, partly deciduous forests and shrubby communities. The correlation is more pronounced at a local scale (macroscopic charcoal), whereas at a regional scale (microscopic charcoal) the vegetation followed the fire intervals with a more marked time lag (10-100 years). Climatic change, such as wetter periods inferred from lake levels, may have directly influenced the vegetational change, exacerbating the effect of human impact. Our study suggests that the disruption of evergreen broadleaved forests occurred when mean fire interval reached values as high as those of today's highly disturbed Mediterranean ecosystems. Hence broadleaved evergreen forests may not be as fire-resilient as assumed according to modern ecological paradigms. In view of the projected increase in fire frequency as a consequence of global warming, the present relict forests of Quercus ilex will be strongly affected.
Keywords: climate change; Fire ecology; Fire history; Holocene; Italy; macroscopic charcoal; Mediterranean vegetation; mesolithic; microscopic charcoal; Neolithic; Quercus ilex; tuscany

Phytoclimatic versatility and potential diversity of natural arboreal forest cover in peninsular Spain - Garcia Lopez, J. M.; ALLUÉ CAMACHO, C. (INVESTIGACION AGRARIA-SISTEMAS Y RECURSOS FORESTALES, 2008)
A multivariate methodology was assayed to evaluate the phytoclimatic versatility of peninsular Spain and how this relates to the potential diversity of natural tree covers. The instances of greatest phytoclimatic versatility occur in a range of altitude between 1000 and 1300 m; these are cool phytoclimates with only short, low-intensity periods of aridity. These factorial ambits of maximum versatility correspond chiefly to the substeppe nemoral subtype VI(VII), followed by genuine nemoral VI and humid nemoromediterranean VI(IV)(2) subtypes. The lowest values of versatility and potential diversity correspond to dry genuine Mediterranean (IV(1)) or transitional Mediterranean IV(VI)(1) subtypes and to alpine oroborealoid or oroarcticoid subtypes. In geographical terms, intermediate mountain areas in the north of the Peninsula and some massifs in the southern half score the highest in the Diversity Index used. The lowest scores are found in the southern half of the Peninsula, although in the northern half low scores are also found for littoral areas, interior areas of the Duero and Ebro basins and alpine areas. Autoecological phytoclimatic spectra headed by stands of Pinus nigra and Quercus petraea present the greatest phytoclimatic versatility, while those headed by Quercus ilex ballota and Pinus uncinata stands present the least versatility. This article offers new methodological horizons for the study of the effects of climate change on plant diversity.
The following values have no corresponding Zotero field: pub-location: CTRA CORUNA KM 7 5, MADRID, 28040, SPAIN publisher: INST NACIONAL INVESTIGACION TECHNOLOGIA AGRARIA ALIMENTARIA
Keywords: Biodiversity; climate change; competition; Simpson Index; suitability

Phytoclimatic versatility and potential diversity of natural arboreal forest cover in peninsular Spain - Garcia Lopez, J M; ALLUÉ CAMACHO, C (INVESTIGACION AGRARIA-SISTEMAS Y RECURSOS FORESTALES, 2008)
A multivariate methodology was assayed to evaluate the phytoclimatic versatility of peninsular Spain and how this relates to the potential diversity of natural tree covers. The instances of greatest phytoclimatic versatility occur in a range of altitude between 1000 and 1300 m; these are cool phytoclimates with only short, low-intensity periods of aridity. These factorial ambits of maximum versatility correspond chiefly to the substeppe nemoral subtype VI(VII), followed by genuine nemoral VI and humid nemoromediterranean VI(IV)(2) subtypes. The lowest values of versatility and potential diversity correspond to dry genuine Mediterranean (IV(1)) or transitional Mediterranean IV(VI)(1) subtypes and to alpine oroborealoid or oroarcticoid subtypes. In geographical terms, intermediate mountain areas in the north of the Peninsula and some massifs in the southern half score the highest in the Diversity Index used. The lowest scores are found in the southern half of the Peninsula, although in the northern half low scores are also found for littoral areas, interior areas of the Duero and Ebro basins and alpine areas. Autoecological phytoclimatic spectra headed by stands of Pinus nigra and Quercus petraea present the greatest phytoclimatic versatility, while those headed by Quercus ilex ballota and Pinus uncinata stands present the least versatility. This article offers new methodological horizons for the study of the effects of climate change on plant diversity.
Keywords: Biodiversity; climate change; competition; Simpson Index; suitability

Environmental heterogeneity, bird-mediated directed dispersal, and oak woodland dynamics in Mediterranean Spain - Purves, Drew W.; Zavala, Miguel A.; Ogle, Kiona; Prieto, Fernando; Benayas, Jose M. Rey (ECOLOGICAL MONOGRAPHS, 2007)
Vegetation dynamics in complex landscapes depend on interactions among environmental heterogeneity, disturbance, habitat fragmentation, and seed dispersal processes. We explore how these features combine to affect the regional abundances and distributions of three Quercus (oak) species in central Spain: Q. faginea (deciduous tree), Q. ilex (evergreen tree), and Q. coccifera (evergreen shrub). We develop and parameterize a stochastic patch occupancy model (SPOM) that, unlike previous SPOMs, includes environmentally driven variation in disturbance and establishment. Dispersal in the model is directed toward local (nearby) suitable habitat patches, following the observed seed-caching behavior of the European Jay. Model parameters were estimated using Bayesian methods and survey data from 12 047 plots. Model simulations were conducted to explore the importance of different dispersal modes (local directed, global directed, local random, global random). The SPOM with local directed dispersal gave a much better fit to the data and reproduced observed regional abundance, abundance-environment correlations, and spatial autocorrelation in abundance for all three species. Model simulations suggest that jay-mediated directed dispersal increases regional abundance and alters species-environment correlations. Local dispersal is estimated to reduce regional abundances, amplify species-environment correlations, and amplify spatial autocorrelation. Parameter estimates and model simulations reveal important species-specific differences in sensitivity to environmental perturbations and dispersal mode. The dominant species Q. ilex is estimated to be highly fecund, but on the edge of its climatic tolerance. Therefore Q. ilex gains little from directed dispersal, suffers little from local dispersal, and is relatively insensitive to changes in habitat cover or disturbance rate; but Q. ilex is highly sensitive to altered drought length. In contrast, the rarest species, Q. coccifera, is well adapted to the climate and soils but has low fecundity; thus, it is highly sensitive to changes in dispersal, habitat cover, and disturbance but insensitive to altered drought length. Finally, Q. faginea is estimated to be both at the edge of its climatic tolerance and to have low fecundity, making it sensitive to all perturbations. Apparently, co-occurring species can exhibit very different interactions among dispersal, environmental characteristics, and physiological tolerances, calling for increased attention to species-specific dynamics in determining regional vegetation responses to anthropogenic perturbations.
The following values have no corresponding Zotero field: pub-location: 1707 H ST NW, STE 400, WASHINGTON, DC 20006-3915 USA publisher: ECOLOGICAL SOC AMER
Keywords: biogeography; climate change; climate envelope; corvids; dispersal limitation; Garrulus; Holm oak; Iberian peninsular; incidence function; patch model; species migration; zoochory

Environmental heterogeneity, bird-mediated directed dispersal, and oak woodland dynamics in Mediterranean Spain - Purves, Drew W; Zavala, MIGUEL a; Ogle, Kiona; Prieto, Fernando; Benayas, Jose M Rey (ECOLOGICAL MONOGRAPHS, 2007)
Vegetation dynamics in complex landscapes depend on interactions among environmental heterogeneity, disturbance, habitat fragmentation, and seed dispersal processes. We explore how these features combine to affect the regional abundances and distributions of three Quercus (oak) species in central Spain: Q. faginea (deciduous tree), Q. ilex (evergreen tree), and Q. coccifera (evergreen shrub). We develop and parameterize a stochastic patch occupancy model (SPOM) that, unlike previous SPOMs, includes environmentally driven variation in disturbance and establishment. Dispersal in the model is directed toward local (nearby) suitable habitat patches, following the observed seed-caching behavior of the European Jay. Model parameters were estimated using Bayesian methods and survey data from 12 047 plots. Model simulations were conducted to explore the importance of different dispersal modes (local directed, global directed, local random, global random). The SPOM with local directed dispersal gave a much better fit to the data and reproduced observed regional abundance, abundance-environment correlations, and spatial autocorrelation in abundance for all three species. Model simulations suggest that jay-mediated directed dispersal increases regional abundance and alters species-environment correlations. Local dispersal is estimated to reduce regional abundances, amplify species-environment correlations, and amplify spatial autocorrelation. Parameter estimates and model simulations reveal important species-specific differences in sensitivity to environmental perturbations and dispersal mode. The dominant species Q. ilex is estimated to be highly fecund, but on the edge of its climatic tolerance. Therefore Q. ilex gains little from directed dispersal, suffers little from local dispersal, and is relatively insensitive to changes in habitat cover or disturbance rate; but Q. ilex is highly sensitive to altered drought length. In contrast, the rarest species, Q. coccifera, is well adapted to the climate and soils but has low fecundity; thus, it is highly sensitive to changes in dispersal, habitat cover, and disturbance but insensitive to altered drought length. Finally, Q. faginea is estimated to be both at the edge of its climatic tolerance and to have low fecundity, making it sensitive to all perturbations. Apparently, co-occurring species can exhibit very different interactions among dispersal, environmental characteristics, and physiological tolerances, calling for increased attention to species-specific dynamics in determining regional vegetation responses to anthropogenic perturbations.
Keywords: biogeography; climate change; climate envelope; corvids; dispersal limitation; Garrulus; Holm oak; Iberian peninsular; incidence function; patch model; species migration; zoochory

GeneticLand: modelling land-use change using evolutionary algorithms - Seixas, J.; Nunes, J. P. (Modelling Land-Use change, 2007)
Future land-use configurations provide valuable knowledge for policy makers and economic agents, especially under expected environmental changes such as decreasing rainfall or increasing temperatures. This chapter proposes an optimisation approach for modelling land-use change in which landscapes (land uses) are generated through the use of an evolutionary algorithm called GeneticLand. It is designed for a multiobjective function that aims at the minimisation of soil erosion and the maximisation of carbon sequestration, under a set of local restrictions. GeneticLand has been applied to a Mediterranean landscape, located in southern Portugal. The algorithm design and the results obtained show the feasibility of the generated landscapes, the appropriateness of the evolutionary methods to model land-use changes and the spatial characteristics of the landscape solutions that emerge when physical drivers have a major influence on their evolution.
The following values have no corresponding Zotero field: periodical: Modelling Land-Use change
Keywords: climate change; evolutionary computing; land use; long-term; Mediterranean landscape.; optimisation; Spatial planning

GeneticLand: modelling land-use change using evolutionary algorithms - Seixas, J; Nunes, J P (Modelling Land-Use change, 2007)
Future land-use configurations provide valuable knowledge for policy makers and economic agents, especially under expected environmental changes such as decreasing rainfall or increasing temperatures. This chapter proposes an optimisation approach for modelling land-use change in which landscapes (land uses) are generated through the use of an evolutionary algorithm called GeneticLand. It is designed for a multiobjective function that aims at the minimisation of soil erosion and the maximisation of carbon sequestration, under a set of local restrictions. GeneticLand has been applied to a Mediterranean landscape, located in southern Portugal. The algorithm design and the results obtained show the feasibility of the generated landscapes, the appropriateness of the evolutionary methods to model land-use changes and the spatial characteristics of the landscape solutions that emerge when physical drivers have a major influence on their evolution.
Keywords: climate change; evolutionary computing; land use; long-term; Mediterranean landscape.; optimisation; Spatial planning

Seasonal soil and leaf CO2 exchange rates in a Mediterranean holm oak forest and their responses to drought conditions - Asensio, Dolores; Penuelas, Josep; Ogaya, Romà; Llusia, Joan (ATMOSPHERIC ENVIRONMENT, 2007)
We measured the soil and leaf CO2 exchange in Quercus ilex and Phillyrea latfolia seasonally throughout the year in a representative site of the Mediterranean region, a natural holm oak forest growing in the Prades Mountains in southeastern Catalonia. In the wet seasons (spring and autumn), we experimentally decreased soil moisture by 30%, by excluding rainfall and water runoff in 12 plots, 1 x 10 m, and left 12 further plots as controls. Our aim was to predict the response of these gas exchanges to the drought forecasted for the next decades for this region by GCM and ecophysiological models. Annual average Soil CO2 exchange rate was 2.27 +/- 0.27 mu mol CO2 m(-2) s(-1). Annual average leaf CO2 exchange rates were 8 +/- 1 and 5 +/- 1 mu mol m(-2) s(-1) in Q. ilex and P. latfolia, respectively. Soil respiration rates in control treatments followed a seasonal pattern similar to photosynthetic activity. They reached maximum values in spring and autumn (2.5-3.8 mu mol m(-2) s(-1) soil CO2 emission rates and 7-15 mu mol m(-2) s(-1) net photosynthetic rates) and minimum values (almost 0 for both variables) in summer, showing that soil moisture was the most important factor driving the soil microbial activity and the photosynthetic activity of plants. In autumn, drought treatment strongly decreased net photosynthesis rates and stomatal conductance of Q. ilex by 44% and 53%, respectively. Soil respiration was also reduced by 43% under drought treatment in the wet seasons. In summer there were larger soil CO2 emissions in drought plots than in control plots, probably driven by autotrophic (roots) metabolism. The results indicate that leaf and Soil CO2 exchange may be strongly reduced (by ca. 44%) by the predicted decreases of soil water availability in the next decades. Long-term studies are needed to confirm these predictions or to find out possible acclimation of those processes. (c) 2006 Elsevier Ltd. All rights reserved.
The following values have no corresponding Zotero field: pub-location: THE BOULEVARD, LANGFORD LANE, KIDLINGTON, OXFORD OX5 1GB, ENGLAND publisher: PERGAMON-ELSEVIER SCIENCE LTD
Keywords: climate change; Drought; foliar net photosynthetic rates; Mediterranean holm oak forest; microorganisms; roots; soil CO2 exchange

Seasonal soil and leaf CO2 exchange rates in a Mediterranean holm oak forest and their responses to drought conditions - Asensio, Dolores; Penuelas, Josep; Ogaya, Romà; Llusia, Joan (ATMOSPHERIC ENVIRONMENT, 2007)
We measured the soil and leaf CO2 exchange in Quercus ilex and Phillyrea latfolia seasonally throughout the year in a representative site of the Mediterranean region, a natural holm oak forest growing in the Prades Mountains in southeastern Catalonia. In the wet seasons (spring and autumn), we experimentally decreased soil moisture by 30%, by excluding rainfall and water runoff in 12 plots, 1 x 10 m, and left 12 further plots as controls. Our aim was to predict the response of these gas exchanges to the drought forecasted for the next decades for this region by GCM and ecophysiological models. Annual average Soil CO2 exchange rate was 2.27 +/- 0.27 mu mol CO2 m(-2) s(-1). Annual average leaf CO2 exchange rates were 8 +/- 1 and 5 +/- 1 mu mol m(-2) s(-1) in Q. ilex and P. latfolia, respectively. Soil respiration rates in control treatments followed a seasonal pattern similar to photosynthetic activity. They reached maximum values in spring and autumn (2.5-3.8 mu mol m(-2) s(-1) soil CO2 emission rates and 7-15 mu mol m(-2) s(-1) net photosynthetic rates) and minimum values (almost 0 for both variables) in summer, showing that soil moisture was the most important factor driving the soil microbial activity and the photosynthetic activity of plants. In autumn, drought treatment strongly decreased net photosynthesis rates and stomatal conductance of Q. ilex by 44% and 53%, respectively. Soil respiration was also reduced by 43% under drought treatment in the wet seasons. In summer there were larger soil CO2 emissions in drought plots than in control plots, probably driven by autotrophic (roots) metabolism. The results indicate that leaf and Soil CO2 exchange may be strongly reduced (by ca. 44%) by the predicted decreases of soil water availability in the next decades. Long-term studies are needed to confirm these predictions or to find out possible acclimation of those processes. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: climate change; Drought; foliar net photosynthetic rates; Mediterranean holm oak forest; microorganisms; roots; soil CO2 exchange

Seasonal soil VOC exchange rates in a Mediterranean holm oak forest and their responses to drought conditions - Asensio, D; Penuelas, J; Ogaya, R; Llusia, J (Atmospheric Environment, 2007)
Available information on soil volatile organic compound (VOC) exchange, emissions and uptake, is very scarce. We here describe the amounts and seasonality of soil VOC exchange during a year in a natural Mediterranean holm oak forest growing in Southern Catalonia. We investigated changes in soil VOC dynamics in drought conditions by decreasing the soil moisture to 30% of ambient conditions by artiﬁcially excluding rainfall and water runoff, and predicted the response of VOC exchange to the drought forecasted in the Mediterranean region for the next decades by GCM and ecophysiological models. The annual average of the total (detected) soil VOC and total monoterpene exchange rates were 3.273.2 and 0.470.3 mg m 2 h 1 , respectively, in control plots. These values represent 0.003% of the total C emitted by soil at the study site as CO2 whereas the annual mean of soil monoterpene exchange represents 0.0004% of total C. Total soil VOC exchange rates in control plots showed seasonal variations following changes in soil moisture and phenology. Maximum values were found in spring (1778 mg m 2 h 1 ). Although there was no signiﬁcant global effect of drought treatment on the total soil VOC exchange rates, annual average of total VOC exchange rates in drought plots resulted in an uptake rate (0.571.8 mg m 2 h 1 ) instead of positive net emission rates. Larger soil VOC and monoterpene exchanges were measured in drought plots than in control plots in summer, which might be mostly attributable to autotrophic (roots) metabolism. The results show that the diversity and magnitude of monoterpene and VOC soil emissions are low compared with plant emissions, that they are driven by soil moisture, that they represent a very small part of the soil-released carbon and that they may be strongly reduced or even reversed into net uptakes by the predicted decreases of soil water availability in the next decades. In all cases, it seems that VOC ﬂuxes in soil might have greater impact on soil ecology than on atmospheric chemistry
Keywords: climate change; Drought; Mediterranean holm oak forest; Monoterpenes; Soil CO2 flux; Soil VOC exchange

Seasonal soil VOC exchange rates in a Mediterranean holm oak forest and their responses to drought conditions - ASENSIO, D.; Penuelas, J.; Ogaya, R.; Llusia, J. (Atmospheric Environment, 2007)
Available information on soil volatile organic compound (VOC) exchange, emissions and uptake, is very scarce. We here describe the amounts and seasonality of soil VOC exchange during a year in a natural Mediterranean holm oak forest growing in Southern Catalonia. We investigated changes in soil VOC dynamics in drought conditions by decreasing the soil moisture to 30% of ambient conditions by artiﬁcially excluding rainfall and water runoff, and predicted the response of VOC exchange to the drought forecasted in the Mediterranean region for the next decades by GCM and ecophysiological models. The annual average of the total (detected) soil VOC and total monoterpene exchange rates were 3.273.2 and 0.470.3 mg m 2 h 1 , respectively, in control plots. These values represent 0.003% of the total C emitted by soil at the study site as CO2 whereas the annual mean of soil monoterpene exchange represents 0.0004% of total C. Total soil VOC exchange rates in control plots showed seasonal variations following changes in soil moisture and phenology. Maximum values were found in spring (1778 mg m 2 h 1 ). Although there was no signiﬁcant global effect of drought treatment on the total soil VOC exchange rates, annual average of total VOC exchange rates in drought plots resulted in an uptake rate (0.571.8 mg m 2 h 1 ) instead of positive net emission rates. Larger soil VOC and monoterpene exchanges were measured in drought plots than in control plots in summer, which might be mostly attributable to autotrophic (roots) metabolism. The results show that the diversity and magnitude of monoterpene and VOC soil emissions are low compared with plant emissions, that they are driven by soil moisture, that they represent a very small part of the soil-released carbon and that they may be strongly reduced or even reversed into net uptakes by the predicted decreases of soil water availability in the next decades. In all cases, it seems that VOC ﬂuxes in soil might have greater impact on soil ecology than on atmospheric chemistry
Keywords: climate change; Drought; Mediterranean holm oak forest; Monoterpenes; Soil CO2 flux; Soil VOC exchange

DESERTIFICATION IN NORTHERN MOROCCO DUE TO EFFECTS OF CLIMATE CHANGE ON GROUNDWATER RECHARGE - Dijck, Simone J. E. Van; Laouina, Abdellah; Carvalho, Anabela V.; Antari, Mostafa; Rocha, Alfredo; Borrego, Carlos; Coen, J. (Desertification in the Mediterranean Region a Security Issue, 2006)
Groundwater resources in Morocco are expected to shrink in the next decades due to an increasing withdrawal for rural and urban development, and a decreasing internal recharge by precipitation under the influence of climate change. The objective of this work is to analyse the recharge of groundwater systems in a region with traditional agriculture and current transformations in northern Morocco (Sehoul region) in response to future climate change and land degradation. Models were used to simulate climate change and effects on surface runoff and groundwater recharge. The climate models indicated increases in temperature and decreases in precipitation in all seasons in 2050 compared to 1990, and an increasing variability of autumn precipitation. Because most cultivated fields are freshly ploughed and sown in autumn, this will increase the risk of desertification due to declining groundwater recharge and increased surface runoff and erosion. This is confirmed by the results of the event-based surface runoff simulation for the 2050 climate. Surface runoff is mainly produced in ancient grazing fields and fallow fields. In view of the current transformation of collective grazing fields into cultivated land, problems with loss of rainfall in surface runoff and soil erosion could be mitigated by 1. early tillage of cultivated fields along the slope contour, followed by leveling, 2. locating cultivated fields downslope of grazing fields to enable the capturing of diffuse surface runoff coming from the grazing fields, and 3. leaving fallow fields untilled and covered with crop remnants. The groundwater modeling results indicate a decrease of the annual groundwater recharge by rainfall of 40-68% from the climate centered in 1990 to the climate centered in 2050. As a result, groundwater levels are predicted to fall up till 2005, but the results are unreliable due to model errors. However, the decreases in precipitation, infiltration and groundwater recharge predicted in this study may be expected to add to the observed trend of groundwater level decrease in the study area, and to continuing desertification.
The following values have no corresponding Zotero field: periodical: Desertification in the Mediterranean Region a Security Issue
Keywords: climate change; Grazing; groundwater; land degradation (voyant); Morocco; Precipitation; surface runoff

DESERTIFICATION IN NORTHERN MOROCCO DUE TO EFFECTS OF CLIMATE CHANGE ON GROUNDWATER RECHARGE - Dijck, Simone J E Van; Laouina, Abdellah; Carvalho, Anabela V; Antari, Mostafa; Rocha, Alfredo; Borrego, Carlos; Coen, J (Desertification in the Mediterranean Region a Security Issue, 2006)
Groundwater resources in Morocco are expected to shrink in the next decades due to an increasing withdrawal for rural and urban development, and a decreasing internal recharge by precipitation under the influence of climate change. The objective of this work is to analyse the recharge of groundwater systems in a region with traditional agriculture and current transformations in northern Morocco (Sehoul region) in response to future climate change and land degradation. Models were used to simulate climate change and effects on surface runoff and groundwater recharge. The climate models indicated increases in temperature and decreases in precipitation in all seasons in 2050 compared to 1990, and an increasing variability of autumn precipitation. Because most cultivated fields are freshly ploughed and sown in autumn, this will increase the risk of desertification due to declining groundwater recharge and increased surface runoff and erosion. This is confirmed by the results of the event-based surface runoff simulation for the 2050 climate. Surface runoff is mainly produced in ancient grazing fields and fallow fields. In view of the current transformation of collective grazing fields into cultivated land, problems with loss of rainfall in surface runoff and soil erosion could be mitigated by 1. early tillage of cultivated fields along the slope contour, followed by leveling, 2. locating cultivated fields downslope of grazing fields to enable the capturing of diffuse surface runoff coming from the grazing fields, and 3. leaving fallow fields untilled and covered with crop remnants. The groundwater modeling results indicate a decrease of the annual groundwater recharge by rainfall of 40-68% from the climate centered in 1990 to the climate centered in 2050. As a result, groundwater levels are predicted to fall up till 2005, but the results are unreliable due to model errors. However, the decreases in precipitation, infiltration and groundwater recharge predicted in this study may be expected to add to the observed trend of groundwater level decrease in the study area, and to continuing desertification.
Keywords: climate change; Grazing; groundwater; land degradation (voyant); Morocco; Precipitation; surface runoff

Potential areas of evergreen forests in Castile and Leon (Spain) according to future climate change - Del Río, Sara; ngel Penas, Á (Phytocoenologia, 2006)
Areas that may potentially be occupied by evergreen forests represent approximately 47% of the total area of the Castile and Leon region. This type of vegetation includes holm-oak (Quercus rotundifolia) and white juniper (Juniperus thurifera) forests. Both of them belong to eight different vegetation series.Considering the observed trends in annual mean temperature and precipitation in Castile and Leon for a thirty-seven-year period (1961?1997), three different hypotheses are put forward in this work to account for climate variations over periods of 25, 50 and 75 years and thus determine the changes that might occur in the areas suited to occupation by evergreen forests.This study also emphasizes the relevance of bioclimatic models for anticipating possible changes in the potential natural vegetation of a territory because of the influence of these changes on land use, conservation and management.Overall, our data support the concept that a decrease in Quercus rotundifolia and Juniperus thurifera forests could occur in Castile and Leon in the near future if the temperature and precipitation trends observed during recent years would remain constant. The main trends indicate an increase in the temperature of winter and decreases in summer. As far as precipitation is concerned, there is an increase in summer and decreases in winter. We conclude that these types of forest may be replaced by deciduous formations.
The following values have no corresponding Zotero field: pub-location: Stuttgart publisher: Schweizerbart'sche Verlagsbuchhandlung
Keywords: bioclimatology; climactic dominion; climate change; evergreen forests

Potential areas of evergreen forests in Castile and Leon (Spain) according to future climate change - Del Río, Sara; ngel Penas, Á (Phytocoenologia, 2006)
Areas that may potentially be occupied by evergreen forests represent approximately 47% of the total area of the Castile and Leon region. This type of vegetation includes holm-oak (Quercus rotundifolia) and white juniper (Juniperus thurifera) forests. Both of them belong to eight different vegetation series.Considering the observed trends in annual mean temperature and precipitation in Castile and Leon for a thirty-seven-year period (1961?1997), three different hypotheses are put forward in this work to account for climate variations over periods of 25, 50 and 75 years and thus determine the changes that might occur in the areas suited to occupation by evergreen forests.This study also emphasizes the relevance of bioclimatic models for anticipating possible changes in the potential natural vegetation of a territory because of the influence of these changes on land use, conservation and management.Overall, our data support the concept that a decrease in Quercus rotundifolia and Juniperus thurifera forests could occur in Castile and Leon in the near future if the temperature and precipitation trends observed during recent years would remain constant. The main trends indicate an increase in the temperature of winter and decreases in summer. As far as precipitation is concerned, there is an increase in summer and decreases in winter. We conclude that these types of forest may be replaced by deciduous formations.
Keywords: bioclimatology; climactic dominion; climate change; evergreen forests

Sensitivity of water and carbon fluxes to climate changes from 1960 to 2100 in European forest ecosystems - Davi, H.; Dufrêne, E.; François, C.; Le Maire, G.; Loustau, D.; Bosc, A.; Rambal, S.; Granier, A.; Moors, E. (Agricultural and Forest Meteorology, 2006)
The effects of climate changes on carbon and water ﬂuxes are quantiﬁed using a physiologically multi-layer, process-based model containing a carbon allocation model and coupled with a soil model (CASTANEA). The model is ﬁrst evaluated on four EUROFLUX sites using eddy covariance data, which provide estimates of carbon and water ﬂuxes at the ecosystem scale. It correctly reproduces the diurnal ﬂuxes and the seasonal pattern. Thereafter simulations were conducted on six French forest ecosystems representative of three climatic areas (oceanic, continental and Mediterranean areas) dominated by deciduous species (Fagus sylvatica, Quercus robur), coniferous species (Pinus pinaster, Pinus sylvestris) or sclerophyllous evergreen species (Quercus ilex). The model is driven by the results of a meteorological model (ARPEGE) following the B2 scenario of IPCC. From 1960 to 2100, the average temperature increases by 3.1 8C (30%) and the rainfall during summer decreases by 68 mm (27%). For all the sites, between the two periods, the simulations predict on average a gross primary production (GPP) increase of 513 g(C) m 2 (+38%). This increase is relatively steep until 2020, followed by a slowing down of the GPP rise due to an increase of the effect of water stress. Contrary to GPP, the ecosystem respiration (Reco ) raises at a constant rate (350 g(C) m 2 i.e. 31% from 1960 to 2100). The dynamics of the net ecosystem productivity (GPP minus Reco ) is the consequence of the effect on both GPP and Reco and differs per site. The ecosystems always remain carbon sinks; however the sink strength globally decreases for coniferous (8%), increases for sclerophyllous evergreen (+34%) and strongly increases for deciduous forest (+67%) that largely beneﬁts by the lengthening of the foliated period. The separately quantiﬁed effects of the main variables (temperature, length of foliated season, CO2 fertilization, drought effect), show that the magnitude of these effects depends on the species and the climatic zone
Keywords: canopy scale; carbon sink; climate change; forest ecosystems; Phenology

Sensitivity of water and carbon fluxes to climate changes from 1960 to 2100 in European forest ecosystems - Davi, H; Dufrêne, E; Francois, C; Le Maire, G; Loustau, D; Bosc, A; Rambal, S; GRANIER, a; Moors, E (Agricultural and Forest Meteorology, 2006)
The effects of climate changes on carbon and water ﬂuxes are quantiﬁed using a physiologically multi-layer, process-based model containing a carbon allocation model and coupled with a soil model (CASTANEA). The model is ﬁrst evaluated on four EUROFLUX sites using eddy covariance data, which provide estimates of carbon and water ﬂuxes at the ecosystem scale. It correctly reproduces the diurnal ﬂuxes and the seasonal pattern. Thereafter simulations were conducted on six French forest ecosystems representative of three climatic areas (oceanic, continental and Mediterranean areas) dominated by deciduous species (Fagus sylvatica, Quercus robur), coniferous species (Pinus pinaster, Pinus sylvestris) or sclerophyllous evergreen species (Quercus ilex). The model is driven by the results of a meteorological model (ARPEGE) following the B2 scenario of IPCC. From 1960 to 2100, the average temperature increases by 3.1 8C (30%) and the rainfall during summer decreases by 68 mm (27%). For all the sites, between the two periods, the simulations predict on average a gross primary production (GPP) increase of 513 g(C) m 2 (+38%). This increase is relatively steep until 2020, followed by a slowing down of the GPP rise due to an increase of the effect of water stress. Contrary to GPP, the ecosystem respiration (Reco ) raises at a constant rate (350 g(C) m 2 i.e. 31% from 1960 to 2100). The dynamics of the net ecosystem productivity (GPP minus Reco ) is the consequence of the effect on both GPP and Reco and differs per site. The ecosystems always remain carbon sinks; however the sink strength globally decreases for coniferous (8%), increases for sclerophyllous evergreen (+34%) and strongly increases for deciduous forest (+67%) that largely beneﬁts by the lengthening of the foliated period. The separately quantiﬁed effects of the main variables (temperature, length of foliated season, CO2 fertilization, drought effect), show that the magnitude of these effects depends on the species and the climatic zone
Keywords: canopy scale; carbon sink; climate change; forest ecosystems; Phenology

Canopy recovery after drought dieback in holm-oak Mediterranean forests of Catalonia (NE Spain) - Lloret, Francisco; Siscart, Daniel; Dalmases, Carles (Global Change Biology, 2004)
Climate change is likely to produce more frequent and longer droughts in the Mediterranean region, like that of 1994, which produced important changes in the Quercus ilex forests, with up to 76% of the trees showing complete canopy dieback. At the landscape level, a mosaic of responses to the drought was observed, linked to the distribution of lithological substrates. Damage to the dominant tree species (Q. ilex) and the most common understorey shrub (Erica arborea) was more noticeable on the compact substrates (breccia) than on the fissured ones (schist). This result was consistent with observations documenting deeper root penetration in schist than in breccia materials, allowing the plants growing on fissured substrates to use water from deeper soil levels. Smaller plants were more vulnerable to drought than larger plants in the trees, but not in the shrubs. Overall, Q. ilex was more affected than E. arborea. The resilience of the system was evaluated from the canopy recovery 1 year after the episode. Stump and crown resprouting was fairly extensive, but the damage pattern in relation to substrate, plant size, and species remained similar. The effect of recurrent drought episodes was studied on vegetation patches of Q. ilex located on mountain slopes and surrounded by bare rock. We observed that plants that resprouted weakly after a previous drought in 1985 were more likely to die or to produce poor regeneration in 1995 than plants that had resprouted vigorously. Vegetation patches located on the lower part of the slope were also less damaged than patches situated uphill. The study provides evidence of relevant changes in forest canopy as a consequence of extreme climate events. The distribution of this effect across the landscape is mediated by lithological substrate, causing patchy patterns. The results also support the hypothesis that recurrent droughts can produce a progressive loss of resilience, by depleting the ability of surviving plants to regenerate.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: climate change; Erica arborea; Quercus ilex; resilience; resprouting; severity; shift; threshold

Establishment of co-existing Mediterranean tree species under a varying soil moisture regime - Lloret, Francisco; Penuelas, Josep; Ogaya, Romà (Journal of Vegetation Science, 2004)
We investigated the responses of two co-existing Mediterranean trees with different regeneration strategies (Phillyrea latifolia seedlings and Quercus ilex sprouts) to experimental drought below the forest canopy. We considered different recruitment stages and used leaf isotopic discrimination to estimate water use efficiency (WUE) and nitrogen availability and use. Drought decreased the emergence and survival of seedlings and sprouts. Survival and growth of older saplings were not influenced by drought. Seedling emergence of P. latifolia was higher than Q. ilex sprout production, but Q. ilex sprouts had higher survival and growth rates. These differences disappeared in the sapling stage. Carbon isotopic discrimination suggested that Q. ilex sprouts had higher WUE than P. latifolia seedlings. Drought increased WUE of recruits, particularly in Q. ilex. Water use regulation increased with ageing, particularly in P. latifolia. Q. ilex had higher δ15N values than P. latifolia; these were also higher under drier soil conditions. Current year seedlings had higher δ15N than saplings, particularly in P. latifolia, suggesting they exploit superficial soil layers. These results suggest that sprouts obtain benefit from resources stored in parent plants. At earlier stages, they perform better than seedlings. This response is not coupled to adult vulnerability to drought for these species, revealing the difficulty of predicting species dynamics during climate change.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: climate change; Drought; mediterranean forest; Nitrogen use; phillyrea latifolia; Quercus ilex; Recruitment; Regeneration; Seedling; sprouting; water use efficiency

Increasing drought decreases phosphorus availability in an evergreen Mediterranean forest - Sardans, Jordi; Penuelas, Josep (Plant and Soil, 2004)
Mediterranean ecosystems are water-limited and frequently also nutrient-limited. We aimed to investigate the effects of increasing drought, as predicted by GCM and eco-physiological models for the next decades, on the P cycle and P plant availability in a Mediterranean forest. We conducted a ﬁeld experiment in a mature evergreen oak forest, establishing four drought-treatment plots and four control plots (150 m2 each). After three years, the runoff and rainfall exclusion reduced an overall 22% the soil moisture, and the runoff exclusion alone reduced it 10%. The reduction of 22% in soil moisture produced a decrease of 40% of the accumulated aboveground plant P content, above all because there was a smaller increase in aerial biomass. The plant leaf P content increased by 100 ± 40 mg m−2 in the control plots, whereas it decreased by 40 ± 40 mg m−2 in the drought plots. The soil Po-NaHCO3 (organic labile-P fraction) increased by 25% in consonance with the increase in litterfall, while the inorganic labile-P fraction decreased in relation to the organic labile-P fraction up to 48%, indicating a decrease in microbial activity. Thus, after just three years of slight drought, a clear trend towards an accumulation of P in the soil and towards a decrease of P in the stand biomass was observed. The P accumulation in the soil in the drought plots was mainly in forms that were not directly available to plants. These indirect effects of drought including the decrease in plant P availability, may
Keywords: climate change; Drought; Mediterranean ecosystems; mineralomasses; nutrient concentrations; nutrient cycles; phosphorus; Quercus ilex; Soil

Increasing drought decreases phosphorus availability in an evergreen Mediterranean forest - Sardans, Jordi; Penuelas, Josep (Plant and Soil, 2004)
Mediterranean ecosystems are water-limited and frequently also nutrient-limited. We aimed to investigate the effects of increasing drought, as predicted by GCM and eco-physiological models for the next decades, on the P cycle and P plant availability in a Mediterranean forest. We conducted a ﬁeld experiment in a mature evergreen oak forest, establishing four drought-treatment plots and four control plots (150 m2 each). After three years, the runoff and rainfall exclusion reduced an overall 22% the soil moisture, and the runoff exclusion alone reduced it 10%. The reduction of 22% in soil moisture produced a decrease of 40% of the accumulated aboveground plant P content, above all because there was a smaller increase in aerial biomass. The plant leaf P content increased by 100 ± 40 mg m−2 in the control plots, whereas it decreased by 40 ± 40 mg m−2 in the drought plots. The soil Po-NaHCO3 (organic labile-P fraction) increased by 25% in consonance with the increase in litterfall, while the inorganic labile-P fraction decreased in relation to the organic labile-P fraction up to 48%, indicating a decrease in microbial activity. Thus, after just three years of slight drought, a clear trend towards an accumulation of P in the soil and towards a decrease of P in the stand biomass was observed. The P accumulation in the soil in the drought plots was mainly in forms that were not directly available to plants. These indirect effects of drought including the decrease in plant P availability, may
Keywords: climate change; Drought; Mediterranean ecosystems; mineralomasses; nutrient concentrations; nutrient cycles; phosphorus; Quercus ilex; Soil

A global change-induced biome shift in the Montseny mountains (NE Spain) - Penuelas, Josep; Boada, Martí (Global Change Biology, 2003)
Shifts in plant species and biome distribution in response to warming have been described in past climate changes. However, reported evidence of such shifts under current climate change is still scarce. By comparing current and 1945 vegetation distribution in the Montseny mountains (Catalonia, NE Spain), we report here a progressive replacement of cold-temperate ecosystems by Mediterranean ecosystems. Beech (Fagus sylvatica) forest has shifted altitudinally upwards by ca. 70 m at the highest altitudes (1600–1700 m). Both the beech forests and the heather (Calluna vulgaris) heathlands are being replaced by holm oak (Quercus ilex) forest at medium altitudes (800–1400 m). This beech replacement has been observed to occur through a progressive isolation and degradation of beech stands. In ‘isolated’ (small and surrounded by holm oaks) beech stands, beech trees are 30% more defoliated, beech recruitment is 41% lower, and holm oak recruitment is three times higher than in ‘continental’ (large and continuous) beech stands. The progressively warmer conditions, complemented by the land use changes (mainly the cessation of traditional land management) are the apparent causes, providing a paradigmatic example of global change affecting distributions of plant species and biomes.
The following values have no corresponding Zotero field: publisher: Blackwell Science, Ltd
Keywords: altitudinal shift; biome replacement; Calluna heathland; climate change; defoliation status; Fagus sylvatica; Land use change; mediterranean forest; Montseny mountains; Quercus ilex; Recruitment; temperate forest

A hydraulic model to predict drought-induced mortality in woody plants: an application to climate change in the Mediterranean - Martínez-Vilalta, J.; Piñol, J.; Beven, K. (Ecological Modelling, 2002)
The potential effects of climate change on vegetation are of increasing concern. In the Mediterranean region, the dominant impact of climate change is expected to be through the modiﬁcation of water balance. In this paper we present a model developed to predict drought-induced mortality of woody plants under different climatic scenarios. The model is physiologically-based and simulates water transport within individual woody plants, which can be isolated or competing for a common water resource. The model assumes that plant mortality is controlled by the carbon balance: when the plant is unable to transport water to the leaves it ceases to acquire carbon and, if this situation lasts long enough, it can no longer survive. In the particular application that we report in this study, two evergreen species are compared, Quercus ilex and Phillyrea latifolia, which were very differently affected by the acute drought that occurred in E Spain in summer 1994. While in some Q. ilex populations the amount of individuals that dried completely was up to 80%, P. latifolia showed almost no damage. During the years 1999 and 2000, canopy transpiration was monitored using sap-ﬂow sensors in individuals of these two species in a Holm-oak forest from NE Spain. A Generalised Likelihood Uncertainty Estimation (GLUE) approach was used to calibrate the model against sap-ﬂow measurements. The only difference between species that was introduced ‘a priori’ was that Q. ilex was more vulnerable to xylem embolism than P. latifolia (based on our own measurements in the study area). During the calibration process the information provided by the measured sap ﬂows was used to retain the more likely parameter sets for each species. These parameter sets were used in all the following simulations. The model was able to accurately simulate transpiration dynamics of the two species in the study area. When the meteorological conditions of summer 1994 were introduced, the model outputs also reproduced the differential impact that drought had on the two species studied. In the simulations under climate change two factors were explored: the increase in mean temperature (+1.5, +3 and +4.5 °C) through its effect on ET , and the duration of summer drought. Under any of the scenarios, mortalities were much higher for Q. ilex: while this species was predicted to survive with less than 5% mortality droughts of up to 84–94 days, the mortality of P. latifolia reached 5% between days 133 and 150. For droughts longer than 3 months, which is approximately the current drought duration in the study area for dry years, the mortality of Q. ilex increased sharply. These results are discussed in relation to the possible long-term impacts of climate change on Q. ilex-dominated forests
Keywords: climate change; drought-induced mortality; Mediterranean ecosystems; Modelling; phillyrea latifolia; Quercus ilex; water transport

Photosynthesis, Soluble and Structural Carbon Compounds in Two Mediterranean Oak Species (Quercus pubescens and Q. ilex) after Lifetime Growth at Naturally Elevated CO2 Concentrations - Blaschke, L.; Schulte, M.; Raschi, A.; Slee, N.; Rennenberg, H.; Polle, A. (Plant Biology, 2001)
Abstract: To study physiological responses of mature forest trees to elevated CO2 after lifetime growth under elevated atmospheric CO2 concentrations (pCO2), photosynthesis, Rubisco content, foliar concentrations of soluble sugars and starch, sugar concentrations in transport tissues (phloem and xylem), structural biomass, and lignin in leaves and branches were investigated in 30- to 50-year-old Quercus pubescens and Q. ilex trees grown at two naturally elevated CO2 springs in Italy. Ribulose-1,5-bisphosphate carboxylase/oxygenase content was decreased in Q. pubescens grown under elevated CO2 concentrations, but not in Q. ilex. Photosynthesis was consistently higher in Q. pubescens grown at elevated CO2 as compared with “control” sites, whereas the response in Q. ilex was less pronounced. Stomatal conductance was lower in both species leading to decreased transpiration and increased instantaneous water use efficiency in Q. pubescens. Overall mean sugar + starch concentrations of the leaves were not affected by elevated pCO2, but phloem exudates contained higher concentrations of soluble sugars. This finding suggests increased transport to sinks. Qualitative changes in major carbon-bearing compounds, such as structural biomass and lignins, were only found in bark but not in other tissues. These results support the concept that the maintenance of increased rates of photosynthesis after long-term acclimation to elevated pCO2 provides a means of optimization of water relations under arid climatic conditions but does not cause an increase in aboveground carbon sequestration per unit of tissue in Mediterranean oak species.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Carbohydrate; climate change; Elevated CO2; Lignin; photosynthesis; Rubisco

Photosynthesis, Soluble and Structural Carbon Compounds in Two Mediterranean Oak Species (Quercus pubescens and Q. ilex) after Lifetime Growth at Naturally Elevated CO2 Concentrations - Blaschke, L; Schulte, M; Raschi, A; Slee, N; Rennenberg, H; Polle, A (Plant Biology, 2001)
Abstract: To study physiological responses of mature forest trees to elevated CO2 after lifetime growth under elevated atmospheric CO2 concentrations (pCO2), photosynthesis, Rubisco content, foliar concentrations of soluble sugars and starch, sugar concentrations in transport tissues (phloem and xylem), structural biomass, and lignin in leaves and branches were investigated in 30- to 50-year-old Quercus pubescens and Q. ilex trees grown at two naturally elevated CO2 springs in Italy. Ribulose-1,5-bisphosphate carboxylase/oxygenase content was decreased in Q. pubescens grown under elevated CO2 concentrations, but not in Q. ilex. Photosynthesis was consistently higher in Q. pubescens grown at elevated CO2 as compared with “control” sites, whereas the response in Q. ilex was less pronounced. Stomatal conductance was lower in both species leading to decreased transpiration and increased instantaneous water use efficiency in Q. pubescens. Overall mean sugar + starch concentrations of the leaves were not affected by elevated pCO2, but phloem exudates contained higher concentrations of soluble sugars. This finding suggests increased transport to sinks. Qualitative changes in major carbon-bearing compounds, such as structural biomass and lignins, were only found in bark but not in other tissues. These results support the concept that the maintenance of increased rates of photosynthesis after long-term acclimation to elevated pCO2 provides a means of optimization of water relations under arid climatic conditions but does not cause an increase in aboveground carbon sequestration per unit of tissue in Mediterranean oak species.
Keywords: Carbohydrate; climate change; Elevated CO2; Lignin; photosynthesis; Rubisco

Modelling the responses to climate change of a Mediterranean forest managed at different thinning intensities: Effects on growth and water fluxes - Gracia, C. A.; Sabate, S.; Tello, E. (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
This study explores the effect of various climatic change scenarios over a 50 year period on plots managed at a range of thinning intensities. In order to determine how management practises can modify the effect of climatic change on Mediterranean Forests we integrated field experiments and the results of the GOTILWA model so as to take into account both water fluxes and forest structure interactions. The results show that the positive effects of atmospheric CO2 fertilisation, causing an increase in WUE, counteract with the negative effects of both temperature increase and rainfall decrease. Thinning might attenuate the effects of adverse conditions by reducing both leaf respiratory costs and the foliage turnover rate.
The following values have no corresponding Zotero field: periodical: IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS pub-location: PO BOX 17, 3300 AA DORDRECHT, NETHERLANDS
Keywords: climate change; mediterranean forest; Modelling

Modelling the responses to climate change of a Mediterranean forest managed at different thinning intensities: Effects on growth and water fluxes - Gracia, C A; Sabate, S; Tello, E (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
This study explores the effect of various climatic change scenarios over a 50 year period on plots managed at a range of thinning intensities. In order to determine how management practises can modify the effect of climatic change on Mediterranean Forests we integrated field experiments and the results of the GOTILWA model so as to take into account both water fluxes and forest structure interactions. The results show that the positive effects of atmospheric CO2 fertilisation, causing an increase in WUE, counteract with the negative effects of both temperature increase and rainfall decrease. Thinning might attenuate the effects of adverse conditions by reducing both leaf respiratory costs and the foliage turnover rate.
Keywords: climate change; mediterranean forest; Modelling

Phytophthora cinnamomi and oak decline in southern Europe. Environmental constraints including climate change - Brasier, C M (Ann. For. Sci., 1996)
One of the most destructive of all tree root pathogens, the oomycete fungus Phytophthora cinnamomi, is associated with mortality and decline of Quercus suber and Q ilex in the Mediterranean region. The symptoms and distribution of this decline are described. P cinnamomi is a primary pathogen on a very wide range of trees and woody ornamentals worldwide, but is probably a native of the Papua New Guinea region. It is soil borne and requires warm, wet soils to infect roots. Since 1900 it has caused major epidemics on native chestnuts in the United States and Europe, and now threatens the stability of entire forest and heath communities ecosystems in some parts of Australia. Together with drought, it may be a major predisposing factor in the Iberian oak decline. Its possible role in this decline including its interaction with drought is discussed, and a generalised working hypothesis of decline is presented. The potential influence of climate warming on the activity of P cinnamomi is also considered. A model based on the CLIMEX program suggests that warming would significantly enhance the activity of the pathogen at its existing disease locations (such as the western Mediterranean and coastal northwest Europe), but that it would not greatly extend its activity into areas with cold winters such as central and eastern Europe
Keywords: climate change; Drought; Oak decline; phytophthora cinnamomi; root pathogen